Negative active material, method for preparing the same, and secondary battery and electric device including the same

CN120674486BActive Publication Date: 2026-10-30CONTEMPORARY AMPEREX TECHNOLOGY CO LTD
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202510837348.4
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2022-11-02
Publication Date
2026-10-30
Estimated Expiration
2042-11-02

AI Technical Summary

Technical Problem

在二次电池高速发展过程中对能量密度提出了更高的要求,石墨是二次电池最常用的负极活性材料,但是石墨的容量发挥已接近其理论比容量372mAh/g,硅由于具有高达4200mAh/g的理论比容量以及较低的成本而引起人们广泛关注,但是,硅在充放电过程中存在巨大的体积效应,易造成颗粒破碎、粉化,进而导致二次电池的首次库伦效率、循环性能和存储性能均较差

Benefits of technology

[0070]本申请提供的负极活性材料能具有高容量、高首次库伦效率和低体积膨胀,并且还能使二次电池更好地兼顾高能量密度、高首次库伦效率、长循环寿命和长存储寿命。本申请的用电装置包括本申请提供的二次电池,因而至少具有与所述二次电池相同的优势。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN120674486B_ABST
    Figure CN120674486B_ABST
Patent Text Reader

Abstract

The application provides a negative electrode active material and a preparation method thereof, a secondary battery containing the negative electrode active material, and an electric device, the negative electrode active material comprising a base material and a silicon-based material, the base material comprising a plurality of pore structures, at least a part of the silicon-based material being located in the pore structures of the base material, at least a part of the silicon-based material being in a crystalline structure, the silicon-based material comprising a first silicon-based material and a second silicon-based material with different grain sizes, and the ratio of the grain size of the first silicon-based material to the grain size of the second silicon-based material being greater than or equal to 1.6; the grain size of the first silicon-based material being greater than 0 and less than or equal to 20 nm, and the grain size of the second silicon-based material being greater than 0 and less than or equal to 12 nm. The negative electrode active material provided by the application has high capacity, high initial coulomb efficiency and low volume expansion, and can make the secondary battery have high energy density, high initial coulomb efficiency, long cycle life and long storage life.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This application belongs to the field of battery technology, specifically relating to a negative electrode active material and its preparation method, as well as a secondary battery and power-consuming device containing the same. Background Technology

[0002] In recent years, rechargeable batteries have been widely used in energy storage power systems such as hydropower, thermal power, wind power, and solar power plants, as well as in power tools, electric bicycles, electric motorcycles, electric vehicles, military equipment, aerospace, and many other fields. The rapid development of rechargeable batteries has placed higher demands on energy density. Graphite is the most commonly used negative electrode active material in rechargeable batteries, but its capacity utilization is already close to its theoretical specific capacity of 372 mAh / g. Silicon has attracted widespread attention due to its theoretical specific capacity of up to 4200 mAh / g and its relatively low cost. However, silicon exhibits a significant volume effect during charge and discharge, easily causing particle breakage and pulverization, which in turn leads to poor initial coulombic efficiency, cycle performance, and storage performance of rechargeable batteries. Summary of the Invention

[0003] The purpose of this application is to provide a negative electrode active material and its preparation method, as well as a secondary battery and power device containing the same, wherein the negative electrode active material has high capacity, high initial coulombic efficiency and low volume expansion, and enables the secondary battery to achieve high energy density, high initial coulombic efficiency, long cycle life and long storage life.

[0004] The first aspect of this application provides a negative electrode active material, the negative electrode active material comprising a matrix material and a silicon-based material, the matrix material comprising a carbon material, the matrix material comprising a plurality of porous structures, at least a portion of the silicon-based material being located in the porous structures of the matrix material, at least a portion of the silicon-based material being a crystalline structure, the silicon-based material comprising a first silicon-based material and a second silicon-based material having different grain sizes, and the ratio of the grain size of the first silicon-based material to the grain size of the second silicon-based material being greater than or equal to 1.6:1.

[0005] The negative electrode active material provided in this application includes a matrix material with multiple porous structures and at least a portion of a silicon-based material located within the porous structures of the matrix material. The silicon-based material includes a first silicon-based material and a second silicon-based material with different grain sizes. The first silicon-based material has a larger grain size, which helps improve the initial coulombic efficiency of the secondary battery. However, the first silicon-based material has large volume expansion and poor structural stability, which is detrimental to improving the cycle performance and reducing the volume expansion of the secondary battery. The second silicon-based material has a smaller grain size, which is beneficial to improving the cycle performance and reducing the volume expansion of the secondary battery. However, its initial coulombic efficiency is lower, resulting in a large actual capacity loss in the secondary battery. The negative electrode active material provided in this application simultaneously includes a first silicon-based material with a larger grain size and a second silicon-based material with a smaller grain size. Therefore, the negative electrode active material provided in this application can have high capacity, high initial coulombic efficiency, and low volume expansion, and can also enable the secondary battery to achieve high energy density, high initial coulombic efficiency, long cycle life, and long storage life.

[0006] In any embodiment of this application, the ratio of the grain size of the first silicon-based material to the grain size of the second silicon-based material is (1.6-4):1, and can be optionally (2-4):1. This allows for better utilization of the first silicon-based material's effect on improving initial coulombic efficiency, as well as the second silicon-based material's effect on improving cycle performance and reducing volume expansion.

[0007] In any embodiment of this application, the grain size of the first silicon-based material is greater than 0 and less than or equal to 20 nm, and can be selected as 2 nm-20 nm. When the first silicon-based material has a suitable grain size, it can improve the initial coulombic efficiency of the secondary battery while avoiding significant adverse effects on the cycle performance and storage performance of the secondary battery.

[0008] In any embodiment of this application, the grain size of the second silicon-based material is greater than 0 and less than or equal to 12 nm, and can be selected as 1 nm-12 nm. When the second silicon-based material has a suitable grain size, it can improve the cycle performance and storage performance of the secondary battery, and also ensure that the secondary battery has a high initial coulombic efficiency.

[0009] In any embodiment of this application, the region formed by extending from the outer surface of the negative electrode active material to the inside of the particle at a distance of 0.5 times the length between any point on the outer surface of the particle and the particle core is denoted as the outer region, and the region inside the outer region is denoted as the inner region. In the cross-sectional image of the negative electrode active material, the total cross-sectional area of ​​the first silicon-based material in the outer region is smaller than the total cross-sectional area of ​​the first silicon-based material in the inner region, and the total cross-sectional area of ​​the second silicon-based material in the inner region is smaller than the total cross-sectional area of ​​the second silicon-based material in the outer region.

[0010] In any embodiment of this application, the ratio α1 of the total cross-sectional area of ​​the first silicon-based material in the outer region to the total cross-sectional area of ​​the first silicon-based material in the inner region is (0-50):100, and can be optionally (0-10):100.

[0011] In any embodiment of this application, the ratio α2 of the total cross-sectional area of ​​the second silicon-based material in the inner region to the total cross-sectional area of ​​the second silicon-based material in the outer region is (0-30):100, and can be optionally (0-10):100.

[0012] By placing the larger-grained first silicon-based material primarily in the internal region of the negative electrode active material and the smaller-grained second silicon-based material primarily in the external region, the advantages of both the first silicon-based material in improving initial coulombic efficiency and the second silicon-based material in improving cycle performance and reducing volume expansion can be fully realized. Therefore, the negative electrode active material provided in this application exhibits high capacity, high initial coulombic efficiency, and low volume expansion, and also enables the secondary battery to better balance high energy density, high initial coulombic efficiency, long cycle life, and long storage life.

[0013] In any embodiment of this application, the cross-sectional image of the negative electrode active material includes a cross-sectional image passing through the particle core of the negative electrode active material.

[0014] In any embodiment of this application, in the outer region of the cross-sectional image of the negative electrode active material, the ratio β1 of the total cross-sectional area of ​​the first silicon-based material to the total cross-sectional area of ​​the second silicon-based material is (0-25):100, optionally (0-5):100, and more preferably, the total cross-sectional area of ​​the first silicon-based material is 0. The outer region of the negative electrode active material mainly contains the second silicon-based material with smaller grain size, and contains no or a small amount of the first silicon-based material with larger grain size. This allows the first silicon-based material to fully enhance the initial coulombic efficiency, while also fully utilizing the second silicon-based material to enhance cycle performance and reduce volume expansion.

[0015] In any embodiment of this application, in the internal region of the cross-sectional image of the negative electrode active material, the ratio β2 of the total cross-sectional area of ​​the first silicon-based material to the total cross-sectional area of ​​the second silicon-based material is 100:(0-250), optionally 100:(0-100). The internal region of the negative electrode active material may contain only the first silicon-based material with a larger grain size, or it may contain a mixture of the first silicon-based material with a larger grain size and the second silicon-based material with a smaller grain size. Furthermore, by further adjusting the total cross-sectional area of ​​the first silicon-based material and the total cross-sectional area of ​​the second silicon-based material within a suitable range, the role of the first silicon-based material in improving the first coulombic efficiency can be better utilized.

[0016] In any embodiment of this application, in the cross-sectional image of the negative electrode active material, the ratio γ1 of the total cross-sectional area of ​​the first silicon-based material to the total cross-sectional area of ​​the negative electrode active material is greater than 0 and less than or equal to 25%, and can be selected as 5%-20%. When the total cross-sectional area of ​​the first silicon-based material is within the above range, the improvement effect of the first silicon-based material on the initial coulombic efficiency can be fully utilized, while avoiding its significant adverse impact on the cycle performance and storage performance of the secondary battery.

[0017] In any embodiment of this application, in the cross-sectional image of the negative electrode active material, the ratio γ2 of the total cross-sectional area of ​​the second silicon-based material to the total cross-sectional area of ​​the negative electrode active material is greater than or equal to 35% and less than 100%, and can be selected as 40%-60%. When the total cross-sectional area of ​​the second silicon-based material is within the above range, the effect of the second silicon-based material on improving cycle performance and reducing volume expansion can be fully utilized, while avoiding its significant adverse impact on the initial coulombic efficiency of the secondary battery.

[0018] In any embodiment of this application, the mass percentage of the first silicon-based material in the silicon-based material is greater than 0 and less than or equal to 40 wt%, and can be selected as 10 wt%-30 wt%. When the content of the first silicon-based material is within the above range, the effect of the first silicon-based material on improving the initial coulombic efficiency can be fully utilized, while avoiding its significant adverse impact on the cycle performance and storage performance of the secondary battery.

[0019] In any embodiment of this application, at least a portion of the silicon-based material is located within the porous structure of the substrate material, and there are voids between the silicon-based material and the substrate material. When there are voids between the silicon-based material and the substrate material, these voids can serve as spaces to accommodate the volume expansion of the silicon-based material, buffering the stress generated during the expansion process.

[0020] In any embodiment of this application, the first silicon-based material includes one or more of elemental silicon, silicon oxide, silicon-carbon material, silicon-nitrogen composite and silicon alloy material, and optionally includes elemental silicon.

[0021] In any embodiment of this application, the second silicon-based material includes one or more of elemental silicon, silicon oxide, silicon-carbon materials, silicon-nitrogen composites, and silicon alloy materials, and optionally includes elemental silicon.

[0022] In any embodiment of this application, the first silicon-based material and the second silicon-based material are made of the same material. Optionally, both the first silicon-based material and the second silicon-based material are elemental silicon.

[0023] In any embodiment of this application, the silicon-based material includes vapor-deposited silicon-based material, and optionally includes vapor-deposited elemental silicon.

[0024] In any embodiment of this application, the first silicon-based material comprises elemental silicon, and the grain size of the first silicon-based material is greater than 0 and less than or equal to 8 nm, optionally between 2 nm and 8 nm. This can improve the initial coulombic efficiency of the secondary battery while avoiding significant adverse effects on the cycle performance and storage performance of the secondary battery; in addition, it also helps to improve the specific capacity of the negative electrode active material.

[0025] In any embodiment of this application, the second silicon-based material comprises elemental silicon, and the grain size of the second silicon-based material is greater than 0 and less than or equal to 5 nm, optionally between 1 nm and 5 nm. This improves both the cycle performance and storage performance of the secondary battery, while ensuring a high initial coulombic efficiency; furthermore, it helps to increase the specific capacity of the negative electrode active material.

[0026] In any embodiment of this application, the porosity of the matrix material is 30%-60%, optionally 40%-50%. When the porosity of the matrix material is within the above range, it is beneficial to accommodate sufficient silicon-based material, thereby improving the energy density of the secondary battery.

[0027] In any embodiment of this application, the matrix material includes a carbon material, which comprises one or more of activated carbon, biomass carbon, pyrolytic carbon, and resin carbon. This not only alleviates the volume expansion of the silicon-based material and improves its conductivity, but also promotes the transport of active ions and increases the specific capacity of the negative electrode active material. Furthermore, it facilitates the dispersion of the silicon-based material.

[0028] In any embodiment of this application, the negative electrode active material further includes a coating layer located on at least a portion of the surface of the substrate material. The coating layer is located on the outer side of the negative electrode active material, thereby further preventing direct contact between the silicon-based material and the electrolyte, reducing the reactivity of the silicon-based material after contact with air, thus reducing electrolyte side reactions, reducing active ion consumption, and improving the cycle performance of the secondary battery.

[0029] In any embodiment of this application, the coating layer comprises one or more of carbon materials, conductive polymers, metal oxides, and metal sulfides.

[0030] In any embodiment of this application, the coating layer comprises a carbon material, optionally including one or more of hard carbon, soft carbon, graphene, carbon fiber, and carbon nanotubes. When the coating layer comprises a carbon material, it also helps to improve the conductivity of the silicon-based material.

[0031] In any embodiment of this application, the thickness of the coating layer is 0 nm-200 nm, and can be selected as 10 nm-150 nm. When the thickness of the coating layer is within the above range, it is beneficial for the negative electrode active material to have high specific capacity and low volume expansion.

[0032] In any embodiment of this application, the negative electrode active material includes carbon and silicon.

[0033] In any embodiment of this application, the mass percentage of carbon in the negative electrode active material is 40wt%-60wt%, and optionally 45wt%-50wt%.

[0034] In any embodiment of this application, the mass percentage of silicon in the negative electrode active material is 38wt%-58wt%, and optionally 40wt%-55wt%.

[0035] When the content of carbon and / or silicon in the negative electrode active material is within the above range, it is beneficial for the negative electrode active material to achieve both high specific capacity and high conductivity.

[0036] In any embodiment of this application, the negative electrode active material further includes other elements, including one or more of oxygen, metal elements, and nitrogen.

[0037] In any embodiment of this application, the sum of the mass percentages of other elements in the negative electrode active material is 0wt%-20wt%, and optionally 0wt%-10wt%.

[0038] In any embodiment of this application, the pore volume of the negative electrode active material is 0.001 cm³. 3 / g-0.02cm 3 / g, can be selected as 0.01cm 3 / g-0.02cm 3 / g. When the pore volume of the negative electrode active material is within the above range, the internal voids of the negative electrode active material are within a suitable range. On the one hand, this can improve the specific capacity and initial coulombic efficiency of the negative electrode active material, and on the other hand, it can buffer the stress generated during the expansion of silicon-based materials.

[0039] In any embodiment of this application, the average particle size Dv50 of the negative electrode active material is 4 μm-12 μm. When the average particle size Dv50 of the negative electrode active material is within the above range, it helps to reduce surface activity, reduce interfacial side reactions, reduce SEI film formation consumption, and also helps to improve the active ion and electron transport performance, thereby further improving the cycle performance of the secondary battery.

[0040] In any embodiment of this application, the BET specific surface area of ​​the negative electrode active material is 1 m². 2 / g-15m 2 / g. When the BET specific surface area of ​​the negative electrode active material is within the above range, it helps to reduce surface activity, reduce interfacial side reactions, reduce SEI film formation consumption, and improve the first coulombic efficiency and cycle performance of the secondary battery.

[0041] A second aspect of this application provides a method for preparing a negative electrode active material, comprising the following steps: providing a matrix material including a plurality of porous structures; the matrix material including a carbon material; dispersing a silicon-based material into the porous structures of the matrix material to obtain the negative electrode active material, wherein the negative electrode active material includes the matrix material and the silicon-based material, the matrix material including a plurality of porous structures, at least a portion of the silicon-based material being located in the porous structures of the matrix material, at least a portion of the silicon-based material being a crystalline structure, the silicon-based material including a first silicon-based material and a second silicon-based material with different grain sizes, and the ratio of the grain size of the first silicon-based material to the grain size of the second silicon-based material being greater than or equal to 1.6:1.

[0042] In any embodiment of this application, the porosity of the matrix material is 30%-60%, optionally 40%-50%. When the porosity of the matrix material is within the above range, it is beneficial for the deposition process to proceed smoothly, and it is also beneficial for the negative electrode active material to have a suitable silicon content, a suitable specific surface area, and / or a suitable pore volume.

[0043] In any embodiment of this application, the matrix material includes carbon materials, which include one or more of graphite materials, activated carbon, biomass carbon, pyrolytic carbon, and resin carbon.

[0044] In any embodiment of this application, the average particle size Dv50 of the substrate material is 4μm-12μm. When the average particle size Dv50 of the substrate material is within the above range, it is beneficial for the deposition process to proceed smoothly, and it is also beneficial for the negative electrode active material to have a suitable silicon content, a suitable specific surface area, and / or a suitable pore volume.

[0045] In any embodiment of this application, the step of dispersing silicon-based material into the porous structure of the matrix material includes the following steps: placing the matrix material including multiple porous structures as a substrate in a reactor, introducing a first mixed gas containing silicon source gas and depositing it at a first temperature T1 for a first time t1, and stopping the introduction of the first mixed gas after the deposition is completed; after the temperature inside the reactor drops to a second temperature T2, introducing a second mixed gas containing silicon source gas and depositing it at a second temperature T2 for a second time t2, and obtaining the negative electrode active material after the deposition is completed. The region formed by extending from the outer surface of the negative electrode active material to the inside of the particle and a distance of 0.5 times the length between any point on the outer surface of the particle and the particle core is called the outer region, and the region inside the outer region is called the inner region. In the cross-sectional image of the negative electrode active material, the total cross-sectional area of ​​the first silicon-based material in the outer region is smaller than the total cross-sectional area of ​​the first silicon-based material in the inner region, and the total cross-sectional area of ​​the second silicon-based material in the inner region is smaller than the total cross-sectional area of ​​the second silicon-based material in the outer region.

[0046] In any embodiment of this application, before introducing the first mixed gas containing silicon source gas, the method further includes the step of: placing a matrix material comprising multiple porous structures as a substrate in a reactor, and performing purging and preheating treatment using a protective gas. Optionally, the preheating temperature is 200℃-300℃. This facilitates the removal of residual moisture in the matrix material, thereby facilitating the subsequent deposition of a first silicon-based material with a larger grain size.

[0047] In any embodiment of this application, the volume percentage V1 of the silicon source gas in the first mixed gas is greater than the volume percentage V2 of the silicon source gas in the second mixed gas. This facilitates the adjustment of the distribution areas of the first silicon-based material and the second silicon-based material, so that the first silicon-based material is mainly located in the internal region of the negative electrode active material, while the second silicon-based material is mainly located in the external region of the negative electrode active material. This allows for the full utilization of both the first silicon-based material's role in improving the initial coulombic efficiency and the second silicon-based material's role in improving cycle performance and reducing volume expansion.

[0048] In any embodiment of the present application, T1>T2. By adjusting the first temperature during deposition to be higher than the second temperature, it is beneficial to adjust the distribution regions of the first silicon-based material and the second silicon-based material, so that the first silicon-based material is mainly located in the inner region of the negative electrode active material, while the second silicon-based material is mainly located in the outer region of the negative electrode active material, thereby not only fully exerting the improvement effect of the first silicon-based material on the initial Coulombic efficiency, but also fully exerting the improvement effect of the second silicon-based material on the cycle performance and the reduction effect on volume expansion.

[0049] In any embodiment of the present application, t1<t2. By adjusting the first time during deposition to be shorter than the second time, it is beneficial to adjust the content and distribution region of the first silicon-based material.

[0050] In any embodiment of the present application, the first mixed gas includes a silicon source gas and a protective gas, optionally, the volume proportion V1 of the silicon source gas in the first mixed gas is 10%-50%.

[0051] In any embodiment of the present application, the total gas flow rate of the first mixed gas is 0.5L / min-20L / min.

[0052] In any embodiment of the present application, the first temperature T1 is 500°C-700°C.

[0053] In any embodiment of the present application, the first time t1 is 0.5h-8h, optionally 0.5h-4h.

[0054] By adjusting at least one of the composition ratio of the first mixed gas, the total gas flow rate of the first mixed gas, the first temperature and the first time within the above ranges, it is beneficial to form the first silicon-based material with a larger grain size, and also beneficial to adjust parameters such as the distribution region and deposition amount of the first silicon-based material.

[0055] In any embodiment of the present application, the second mixed gas includes a silicon source gas and a protective gas, optionally, the volume proportion V2 of the silicon source gas in the second mixed gas is 10%-25%.

[0056] In any embodiment of the present application, the total gas flow rate of the second mixed gas is 0.5L / min-20L / min.

[0057] In any embodiment of the present application, the second temperature T2 is 500°C-600°C.

[0058] In any embodiment of the present application, the second time t2 is 4h-20h, optionally 4h-16h.

[0059] By adjusting at least one of the composition ratio of the second mixed gas, the total gas flow rate of the second mixed gas, the second temperature, and the second time to be within the above range, it is beneficial to form a second silicon-based material with a smaller grain size, and it is also beneficial to adjust parameters such as the distribution area and deposition amount of the second silicon-based material.

[0060] In any embodiment of this application, the total gas flow rate of the second mixture is the same as the total gas flow rate of the first mixture.

[0061] In any embodiment of this application, the method further includes the step of forming a coating layer on at least the surface of the obtained negative electrode active material, the coating layer comprising one or more of carbon materials, conductive polymers, metal oxides and metal sulfides.

[0062] In any embodiment of this application, the step of forming the coating layer includes the following steps: placing the obtained negative electrode active material in a reactor, introducing a third mixed gas containing carbon source gas, and depositing it at a third temperature T3 for a third time t3 to obtain a carbon-coated negative electrode active material. This facilitates the formation of a uniform carbon layer.

[0063] In any embodiment of this application, the third mixed gas includes a carbon source gas and a protective gas. Optionally, the volume percentage V3 of the carbon source gas in the third mixed gas is 10%-50%.

[0064] In any embodiment of this application, the total gas flow rate of the third mixed gas is 0.5 L / min to 20 L / min.

[0065] In any embodiment of this application, the third temperature T3 is 600℃-800℃.

[0066] In any embodiment of this application, the third time t3 is 0.5h-4h.

[0067] By adjusting at least one of the composition ratio of the third mixed gas, the total gas flow rate of the third mixed gas, the third temperature, and the third time to be within the above range, it is beneficial to form a coating layer of appropriate thickness and avoid the coating layer being too thick, which would reduce the initial coulombic efficiency and / or specific capacity of the negative electrode active material.

[0068] A third aspect of this application provides a secondary battery, including a negative electrode sheet, wherein the negative electrode sheet comprises the negative electrode active material described in the first aspect of this application or the negative electrode active material prepared by the preparation method described in the second aspect of this application.

[0069] The fourth aspect of this application provides an electrical device that includes the secondary battery of the third aspect of this application.

[0070] The negative electrode active material provided in this application possesses high capacity, high initial coulombic efficiency, and low volume expansion, and also enables secondary batteries to better balance high energy density, high initial coulombic efficiency, long cycle life, and long storage life. The power device of this application includes the secondary battery provided in this application, and therefore possesses at least the same advantages as the aforementioned secondary battery. Attached Figure Description

[0071] To more clearly illustrate the technical solutions of the embodiments of this application, the accompanying drawings used in the embodiments of this application will be briefly described below. Obviously, the drawings described below are only some embodiments of this application. For those skilled in the art, other drawings can be obtained based on the drawings without creative effort.

[0072] Figure 1 This is a schematic diagram of a cross-sectional image of the negative electrode active material of this application.

[0073] Figure 2 This is a schematic diagram of one embodiment of the battery cell of this application.

[0074] Figure 3 This is an exploded view of one embodiment of the battery cell of this application.

[0075] Figure 4 This is a schematic diagram of one embodiment of the battery module of this application.

[0076] Figure 5 This is a schematic diagram of one embodiment of the battery pack of this application.

[0077] Figure 6 yes Figure 5 An exploded view of an embodiment of the battery pack shown.

[0078] Figure 7 This is a schematic diagram of one embodiment of an electrical device that uses a secondary battery as a power source, as described in this application.

[0079] In the accompanying drawings, the figures may not be drawn to scale. The reference numerals are explained as follows: 1 Battery pack, 2 Upper casing, 3 Lower casing, 4 Battery module, 5 Battery cell, 51 Casing, 52 Electrode assembly, 53 Cover plate, 100 Negative electrode active material, 101 External region, 102 Internal region, O Particle core. Detailed Implementation

[0080] The following detailed description, with appropriate reference to the accompanying drawings, discloses the negative electrode active material of this application, its preparation method, and embodiments of secondary batteries and power-consuming devices comprising the same. However, unnecessary detailed descriptions may be omitted. For example, detailed descriptions of well-known matters and repetitive descriptions of practically identical structures may be omitted. This is to avoid unnecessarily lengthy descriptions and to facilitate understanding by those skilled in the art. Furthermore, the accompanying drawings and the following description are provided for the purpose of enabling those skilled in the art to fully understand this application and are not intended to limit the subject matter of the claims.

[0081] The "range" disclosed in this application is defined by a lower limit and an upper limit. A given range is defined by selecting a lower limit and an upper limit, which define the boundaries of a particular range. Ranges defined in this way can include or exclude endpoints and can be arbitrarily combined; that is, any lower limit can be combined with any upper limit to form a range. For example, if ranges of 60-120 and 80-110 are listed for a specific parameter, it is expected that ranges of 60-110 and 80-120 are also included. Furthermore, if minimum range values ​​of 1 and 2 are listed, and if maximum range values ​​of 3, 4, and 5 are listed, then the following ranges are all expected: 1-3, 1-4, 1-5, 2-3, 2-4, and 2-5. In this application, unless otherwise stated, the numerical range "ab" represents a shortened representation of any combination of real numbers between a and b, where a and b are real numbers. For example, the numerical range "0-5" indicates that all real numbers between "0-5" have been listed in this article; "0-5" is simply a shortened representation of these numerical combinations. Furthermore, when a parameter is stated as an integer ≥2, it is equivalent to disclosing that the parameter is, for example, an integer such as 2, 3, 4, 5, 6, 7, 8, 9, 10, 11, 12, etc.

[0082] Unless otherwise specified, all embodiments and optional embodiments of this application may be combined with each other to form new technical solutions, and such technical solutions should be considered to be included in the disclosure of this application.

[0083] Unless otherwise specified, all technical features and optional technical features of this application may be combined to form new technical solutions, and such technical solutions shall be deemed to be included in the disclosure of this application.

[0084] Unless otherwise specified, all steps in this application may be performed sequentially or randomly, preferably sequentially. For example, the method includes steps (a) and (b), indicating that the method may include steps (a) and (b) performed sequentially, or it may include steps (b) and (a) performed sequentially. For example, the mention that the method may also include step (c) indicates that step (c) may be added to the method in any order. For example, the method may include steps (a), (b), and (c), or it may include steps (a), (c), and (b), or it may include steps (c), (a), and (b), etc.

[0085] Unless otherwise specified, the terms "comprising" and "including" as used in this application can be open-ended or closed-ended. For example, "comprising" and "including" can mean that other components not listed may also be included, or that only the listed components may be included.

[0086] Unless otherwise specified, the term "or" is inclusive in this application. For example, the phrase "A or B" means "A, B, or both A and B". More specifically, the condition "A or B" is satisfied by any of the following conditions: A is true (or exists) and B is false (or does not exist); A is false (or does not exist) and B is true (or exists); or both A and B are true (or exist).

[0087] Unless otherwise specified, in this application, the terms "first," "second," etc., are used to distinguish different objects, rather than to describe a specific order or primary / secondary relationship.

[0088] In this application, the terms "multiple" or "various" refer to two or more kinds of things.

[0089] In this application, "mainly located in" a specific region (e.g., an internal region or an external region) means that at least half of the corresponding material (e.g., a first silicon-based material or a second silicon-based material) is located in that specific region, and also includes the case where all of the corresponding material (e.g., a first silicon-based material or a second silicon-based material) is located in that specific region (e.g., an internal region or an external region).

[0090] Unless otherwise stated, the terms used in this application have the common meanings as commonly understood by those skilled in the art.

[0091] Unless otherwise stated, the values ​​of the parameters mentioned in this application can be determined using various testing methods commonly used in the art, for example, according to the testing methods given in the embodiments of this application.

[0092] Silicon possesses a theoretical specific capacity as high as 4200 mAh / g, which can significantly improve the energy density of secondary batteries. Silicon also has a voltage plateau slightly higher than graphite, making it less prone to dendrite formation on the negative electrode and improving the safety performance of secondary batteries. Furthermore, silicon is widely distributed in the Earth's crust, abundant in resources, and inexpensive, thus reducing the production cost of secondary batteries. Therefore, materials containing silicon (hereinafter referred to as silicon-based materials) have become highly promising negative electrode active materials.

[0093] However, silicon-based materials also have some drawbacks. Unlike carbon-based materials such as graphite, silicon-based materials react with metals (such as lithium and sodium) through alloying reactions during charging and discharging. This results in a significant volume effect, making the particles prone to breakage and pulverization, which in turn leads to pulverization of the negative electrode film and loss of electrical contact with the current collector. Furthermore, the volume effect of silicon-based materials causes repeated damage and reconstruction of the solid electrolyte interphase (SEI) film on the particle surface, further increasing the irreversible consumption of active ions and ultimately affecting the capacity of the secondary battery. Therefore, when silicon-based materials are used as negative electrode active materials, they typically suffer from high irreversible capacity, low initial coulombic efficiency, and large volume expansion, resulting in significant actual capacity loss and poor cycle life in secondary batteries.

[0094] In addition, silicon is a semiconductor material with low intrinsic conductivity. When used as a negative electrode active material, it can affect the capacity volatilization of the secondary battery or require an additional amount of conductive agent, which reduces the actual coating weight of the negative electrode active material and affects the energy density of the secondary battery.

[0095] Currently, the main modification methods for addressing the above problems include the following aspects.

[0096] (1) Reducing the size of silicon-based materials to the nanoscale can alleviate their volume effect. However, the inventors of this application have found that the high specific surface area of ​​nano-silicon-based materials can further exacerbate interfacial side reactions, increase the irreversible consumption of active ions, and reduce the first coulombic efficiency.

[0097] (2) Prepare porous silicon-based materials to mitigate the volume effect by utilizing their own deformation. However, the inventors of this application have found that when using porous silicon-based materials, the volume effect cannot be effectively mitigated, and the improvement on the first coulomb efficiency is also limited.

[0098] (3) Coating the surface of silicon-based materials with a conductive carbon layer increases the conductivity of silicon-based materials and alleviates the volume effect. However, the inventors of this application have found that when the conductive carbon layer is too thin, the coating is incomplete, which leads to rapid capacity decay and short cycle life of the secondary battery; when the conductive carbon layer is too thick, its rigidity is too strong, and the secondary battery is more prone to breakage and pulverization during charging and discharging, thus limiting the improvement of the first coulombic efficiency.

[0099] Therefore, none of the above modification methods can enable secondary batteries to simultaneously achieve high energy density, high initial coulombic efficiency, low volume expansion, and long cycle life.

[0100] In view of this, the inventors of this application have proposed a novel negative electrode active material through extensive research, which has high capacity, high initial coulombic efficiency and low volume expansion, and enables secondary batteries to achieve high energy density, high initial coulombic efficiency, long cycle life and long storage life.

[0101] Negative electrode active materials

[0102] The first aspect of this application provides a negative electrode active material. The negative electrode active material includes a matrix material and a silicon-based material. The matrix material includes a plurality of porous structures, at least a portion of which is located within the porous structures of the matrix material. At least a portion of the silicon-based material has a crystalline structure. The silicon-based material includes a first silicon-based material and a second silicon-based material with different grain sizes, and the ratio of the grain size of the first silicon-based material to the grain size of the second silicon-based material is greater than or equal to 1.6:1.

[0103] The negative electrode active material provided in this application includes a matrix material with multiple porous structures and at least a portion of a silicon-based material located within the porous structures of the matrix material. The silicon-based material includes a first silicon-based material and a second silicon-based material with different grain sizes. The first silicon-based material has a larger grain size, which helps improve the initial coulombic efficiency of the secondary battery. However, the first silicon-based material has large volume expansion and poor structural stability, which is detrimental to improving the cycle performance and reducing the volume expansion of the secondary battery. The second silicon-based material has a smaller grain size, which is beneficial to improving the cycle performance and reducing the volume expansion of the secondary battery. However, its initial coulombic efficiency is lower, resulting in a large actual capacity loss in the secondary battery. The negative electrode active material provided in this application simultaneously includes a first silicon-based material with a larger grain size and a second silicon-based material with a smaller grain size. Therefore, the negative electrode active material provided in this application can have high capacity, high initial coulombic efficiency, and low volume expansion, and can also enable the secondary battery to achieve high energy density, high initial coulombic efficiency, long cycle life, and long storage life.

[0104] In some embodiments, the ratio of the grain size of the first silicon-based material to the grain size of the second silicon-based material is (1.6-4):1, optionally (2-4):1. This allows for better utilization of the first silicon-based material's effect on improving initial coulombic efficiency and the second silicon-based material's effect on improving cycle performance and reducing volume expansion.

[0105] In some embodiments, the grain size of the first silicon-based material is greater than 0 and less than or equal to 20 nm, for example, it can be a range of values ​​including 2 nm, 3 nm, 4 nm, 5 nm, 6 nm, 7 nm, 8 nm, 9 nm, 10 nm, 11 nm, 12 nm, 13 nm, 14 nm, 15 nm, 16 nm, 17 nm, 18 nm, 19 nm, 20 nm, or any combination thereof. Optionally, the grain size of the first silicon-based material is 2 nm to 20 nm. A larger grain size of the first silicon-based material is beneficial for improving the initial coulombic efficiency of the secondary battery, but detrimental to the cycle performance and storage performance of the secondary battery. Therefore, when the first silicon-based material has a suitable grain size, it can improve the initial coulombic efficiency of the secondary battery while avoiding significant adverse effects on the cycle performance and storage performance of the secondary battery.

[0106] In some embodiments, the grain size of the second silicon-based material is greater than 0 and less than or equal to 12 nm, for example, it can be a range of 1 nm, 2 nm, 2.5 nm, 3 nm, 3.5 nm, 4 nm, 4.5 nm, 5 nm, 6 nm, 7 nm, 8 nm, 9 nm, 10 nm, 11 nm, 12 nm, or any combination thereof. Optionally, the grain size of the second silicon-based material is 1 nm to 12 nm. A smaller grain size of the second silicon-based material is beneficial for improving the cycle performance and storage performance of the secondary battery, but it is detrimental to the first coulombic efficiency of the secondary battery. Therefore, when the second silicon-based material has a suitable grain size, it can improve both the cycle performance and storage performance of the secondary battery, while also ensuring a high first coulombic efficiency.

[0107] The grain sizes of the first and second silicon-based materials are known in the art and can be determined using instruments and methods known in the art. For example, they can be measured using a high-resolution transmission electron microscope (HRTEM).

[0108] The region defined by extending from the outer surface of the negative electrode active material towards the interior of the particle at a distance 0.5 times the length between any point on the outer surface of the particle and the particle core is denoted as the outer region, and the region inside the outer region is denoted as the inner region. In some embodiments, in a cross-sectional image of the negative electrode active material, the total cross-sectional area of ​​the first silicon-based material in the outer region is smaller than the total cross-sectional area of ​​the first silicon-based material in the inner region, and the total cross-sectional area of ​​the second silicon-based material in the inner region is smaller than the total cross-sectional area of ​​the second silicon-based material in the outer region.

[0109] By placing the larger-grained first silicon-based material primarily in the internal region of the negative electrode active material and the smaller-grained second silicon-based material primarily in the external region, the advantages of both the first silicon-based material in improving initial coulombic efficiency and the second silicon-based material in improving cycle performance and reducing volume expansion can be fully realized. Therefore, the negative electrode active material provided in this application exhibits high capacity, high initial coulombic efficiency, and low volume expansion, and also enables the secondary battery to better balance high energy density, high initial coulombic efficiency, long cycle life, and long storage life.

[0110] In this application, the description "the total cross-sectional area of ​​the first silicon-based material in the outer region is less than the total cross-sectional area of ​​the first silicon-based material in the inner region" is not limited to the outer region necessarily containing the first silicon-based material. When the outer region does not contain the first silicon-based material, and the total cross-sectional area of ​​the first silicon-based material in the outer region is 0, it is also considered to satisfy "the total cross-sectional area of ​​the first silicon-based material in the outer region is less than the total cross-sectional area of ​​the first silicon-based material in the inner region".

[0111] In this application, the description "the total cross-sectional area of ​​the second silicon-based material in the inner region is less than the total cross-sectional area of ​​the second silicon-based material in the outer region" is not limited to the inner region necessarily containing the second silicon-based material. When the inner region does not contain the second silicon-based material, and the total cross-sectional area of ​​the second silicon-based material in the inner region is 0, it is also considered that "the total cross-sectional area of ​​the second silicon-based material in the inner region is less than the total cross-sectional area of ​​the second silicon-based material in the outer region" is satisfied.

[0112] In this application, a cross-section of the negative electrode active material particles can be prepared using dual-beam focused ion beam microscopy (DIB-SEM). This cross-section passes through the central region of the negative electrode active material, optionally through the particle core. The cross-sectional image features of the negative electrode active material can then be observed using transmission electron microscopy (TEM) or high-resolution transmission electron microscopy (HRTEM). When observing the cross-sectional image of the negative electrode active material, the areas of the lattice fringe regions formed by the first silicon-based material and the second silicon-based material are different, thereby making it easy to distinguish between the first silicon-based material and the second silicon-based material.

[0113] In this application, the cross-sectional image of the negative electrode active material includes a cross-sectional image passing through the particle core of the negative electrode active material.

[0114] In this application, "particle core" refers to the intersection of the longest diameter (or longest diagonal) and the shortest diameter (or shortest diagonal) of the negative electrode active material particle.

[0115] Figure 1 This is a schematic diagram of a cross-sectional image of the negative electrode active material 100 of this application, and the cross-sectional image passes through the particle core O of the negative electrode active material 100. Figure 1 As shown, the negative electrode active material 100 includes an outer region 101 and an inner region 102 located inside the outer region 101. The intersection of the longest diameter (or longest diagonal) and the shortest diameter (or shortest diagonal) of the negative electrode active material particle is the particle core O. The length between any point P on the outer surface of the particle and the particle core O is denoted as R. n The length R between any point P on the outer surface of the negative electrode active material particle and the particle core O extends from the outer surface of the particle towards the inside of the particle. n The region formed by a distance of 0.5 times the distance is denoted as the outer region 101.

[0116] It should be noted that "length R" here refers to... n "R" refers to the length of any point on the outer surface of the particle from the particle core. When the negative electrode active material has a regular or irregular morphology other than an ideal sphere, the length R is... n This is expressed as a variable value, meaning the distance from the particle core to different locations on the outer surface of the particle is a constantly changing numerical value. Therefore, the distance extending from different locations on the outer surface of the particle into the particle is also a constantly changing numerical value. Thus, the corresponding distance (i.e., 0.5R) extends from all points on the outer surface of the negative electrode active material particle into the particle into the particle... n The area enclosed by all the points obtained afterward and the outer surface of the particle is the outer region.

[0117] In some embodiments, in the cross-sectional image of the negative electrode active material, the ratio α1 of the total cross-sectional area of ​​the first silicon-based material in the outer region to the total cross-sectional area of ​​the first silicon-based material in the inner region is (0-50):100, optionally (0-40):100, (0-30):100, (0-20):100, (0-15):100, (0-10):100, (0-5):100. In some embodiments, in the cross-sectional image of the negative electrode active material, the ratio α1 of the total cross-sectional area of ​​the first silicon-based material in the outer region to the total cross-sectional area of ​​the first silicon-based material in the inner region is 0, that is, the aforementioned outer region of the negative electrode active material does not contain first silicon-based material with a large grain size.

[0118] By placing the first silicon-based material primarily within the internal region of the negative electrode active material, the improvement effect of the first silicon-based material on the initial coulombic efficiency can be fully utilized, while avoiding significant adverse effects on the cycle performance and storage performance of the secondary battery.

[0119] In some embodiments, in the cross-sectional image of the negative electrode active material, the ratio α2 of the total cross-sectional area of ​​the second silicon-based material in the inner region to the total cross-sectional area of ​​the second silicon-based material in the outer region is (0-30):100, optionally (0-25):100, (0-20):100, (0-15):100, (0-10):100, or (0-5):100. In some embodiments, the ratio α2 of the total cross-sectional area of ​​the second silicon-based material in the inner region to the total cross-sectional area of ​​the second silicon-based material in the outer region is 0, that is, the aforementioned inner region of the negative electrode active material does not contain second silicon-based material with small grain size.

[0120] By placing the second silicon-based material primarily in the external region of the negative electrode active material, the role of the second silicon-based material in improving cycle performance and reducing volume expansion can be fully utilized.

[0121] In some embodiments, in the outer region of the cross-sectional image of the negative electrode active material, the ratio β1 of the total cross-sectional area of ​​the first silicon-based material to the total cross-sectional area of ​​the second silicon-based material is (0-25):100, optionally (0-20):100, (0-15):100, (0-10):100, (0-5):100. More preferably, the total cross-sectional area of ​​the first silicon-based material is 0, meaning that the aforementioned outer region of the negative electrode active material does not contain the first silicon-based material with a larger grain size. The outer region of the negative electrode active material mainly contains the second silicon-based material with a smaller grain size, and contains no or a small amount of the first silicon-based material with a larger grain size. This allows the first silicon-based material to fully enhance the initial coulombic efficiency, while also fully utilizing the second silicon-based material to enhance cycle performance and reduce volume expansion.

[0122] In some embodiments, in the internal region of the cross-sectional image of the negative electrode active material, the ratio β2 of the total cross-sectional area of ​​the first silicon-based material to the total cross-sectional area of ​​the second silicon-based material is 100:(0-250), optionally 100:(0-100), 100:(0-80), 100:(0-60), 100:(0-40), 100:(0-30), 100:(0-20), 100:(0-10), or 100:(0-5). The internal region of the negative electrode active material may contain only the first silicon-based material with a larger grain size, or it may contain a mixture of the first silicon-based material with a larger grain size and the second silicon-based material with a smaller grain size. Furthermore, by further adjusting the total cross-sectional area of ​​the first silicon-based material and the total cross-sectional area of ​​the second silicon-based material within a suitable range, the role of the first silicon-based material in improving the first coulombic efficiency can be better utilized.

[0123] In some embodiments, in the cross-sectional image of the negative electrode active material, the ratio γ1 of the total cross-sectional area of ​​the first silicon-based material to the total cross-sectional area of ​​the negative electrode active material is greater than 0 and less than or equal to 25%, for example, it can be a range of any value consisting of 5%, 6%, 7%, 8%, 9%, 10%, 11%, 12%, 13%, 14%, 15%, 16%, 17%, 18%, 19%, 20%, 21%, 22%, 23%, 24%, 25%, or more. Optionally, the ratio γ1 of the total cross-sectional area of ​​the first silicon-based material to the total cross-sectional area of ​​the negative electrode active material is 5%-20%, 8%-20%, 10%-20%, 12%-20%, or 12%-18%.

[0124] When the total cross-sectional area of ​​the first silicon-based material is within the above range, it can fully leverage the role of the first silicon-based material in improving the initial coulombic efficiency, while avoiding significant adverse effects on the cycle performance and storage performance of the secondary battery.

[0125] In some embodiments, in the cross-sectional image of the negative electrode active material, the ratio γ2 of the total cross-sectional area of ​​the second silicon-based material to the total cross-sectional area of ​​the negative electrode active material is greater than or equal to 35% and less than 100%, and can be selected as 40%-65%, 40%-60%, 40%-55%, or 40%-50%.

[0126] When the total cross-sectional area of ​​the second silicon-based material is within the above range, it can fully leverage the role of the second silicon-based material in improving cycle performance and reducing volume expansion, while avoiding a significant adverse impact on the initial coulombic efficiency of the secondary battery.

[0127] In some embodiments, the mass percentage of the first silicon-based material in the silicon-based material is greater than 0 and less than or equal to 40 wt%, for example, it can be a range consisting of any value of 5 wt%, 10 wt%, 15 wt%, 20 wt%, 25 wt%, 30 wt%, 35 wt%, 40 wt%, or more. Optionally, the mass percentage of the first silicon-based material in the silicon-based material is 5 wt%-40 wt%, 5 wt%-35 wt%, 10 wt%-35 wt%, or 10 wt%-30 wt%.

[0128] When the content of the first silicon-based material is within the above range, it can fully leverage the role of the first silicon-based material in improving the initial coulombic efficiency, while avoiding its significant adverse impact on the cycle performance and storage performance of the secondary battery.

[0129] In some embodiments, at least a portion of the silicon-based material is located within the porous structure of the substrate material, and there are voids between the silicon-based material and the substrate material. When there are voids between the silicon-based material and the substrate material, these voids can serve as spaces to accommodate the volume expansion of the silicon-based material, buffering the stress generated during the expansion process.

[0130] In some embodiments, the first silicon-based material includes one or more of elemental silicon, silicon oxide, silicon-carbon materials, silicon-nitrogen composites, and silicon alloy materials, and optionally includes elemental silicon.

[0131] In some embodiments, the second silicon-based material includes one or more of elemental silicon, silicon oxide, silicon-carbon materials, silicon-nitrogen composites, and silicon alloy materials, and optionally includes elemental silicon.

[0132] In some embodiments, the first silicon-based material and the second silicon-based material are made of the same material; optionally, both the first silicon-based material and the second silicon-based material are elemental silicon.

[0133] In some embodiments, the first silicon-based material comprises elemental silicon, and the grain size of the first silicon-based material is greater than 0 and less than or equal to 8 nm, for example, it can be a range of any values ​​including 2 nm, 3 nm, 4 nm, 5 nm, 6 nm, 7 nm, 8 nm, or higher. Optionally, the grain size of the first silicon-based material is 2 nm to 8 nm. In this case, when the first silicon-based material has a suitable grain size, it can improve the initial coulombic efficiency of the secondary battery while avoiding significant adverse effects on the cycle performance and storage performance of the secondary battery; in addition, it also helps to improve the specific capacity of the negative electrode active material.

[0134] In some embodiments, the second silicon-based material comprises elemental silicon, and the grain size of the second silicon-based material is greater than 0 and less than or equal to 5 nm, for example, it can be a range of any values ​​including 1 nm, 2 nm, 2.5 nm, 3 nm, 3.5 nm, 4 nm, 4.5 nm, 5 nm, or more. Optionally, the grain size of the second silicon-based material is 1 nm to 5 nm. In this case, when the second silicon-based material has a suitable grain size, it can improve the cycle performance and storage performance of the secondary battery, and also ensure that the secondary battery has a high initial coulombic efficiency; in addition, it also helps to improve the specific capacity of the negative electrode active material.

[0135] In some embodiments, the silicon-based material includes vapor-deposited silicon-based material, optionally including vapor-deposited elemental silicon.

[0136] The matrix material includes multiple porous structures, and at least a portion of the silicon-based material is located within the porous structure of the matrix material. This allows the matrix material to effectively mitigate the volume expansion of the silicon-based material and prevent the silicon-based material or the negative electrode active material from breaking or pulverizing.

[0137] In some embodiments, the porosity of the matrix material is 30%-60%, for example, it can be a range consisting of any value of 30%, 35%, 40%, 45%, 50%, 55%, 60%, or higher. Optionally, the porosity of the matrix material is 40%-50%.

[0138] When the porosity of the matrix material is within the above range, it is beneficial to accommodate sufficient silicon-based material, which in turn helps to improve the energy density of the secondary battery.

[0139] In some embodiments, the matrix material comprises a carbon material. The matrix material includes multiple porous structures, which can mitigate the volume expansion of the silicon-based material and improve its electrical conductivity.

[0140] In some embodiments, the matrix material includes graphite materials, such as natural graphite. This not only alleviates the volume expansion of silicon-based materials and improves their conductivity, but also promotes the transport of active ions and increases the specific capacity of the negative electrode active material.

[0141] In some embodiments, the matrix material comprises a carbon material, which includes one or more of activated carbon, biomass carbon, pyrolytic carbon, and resin carbon. This not only alleviates the volume expansion of silicon-based materials and improves their conductivity, but also promotes the transport of active ions and increases the specific capacity of the negative electrode active material. Furthermore, compared to graphite materials, carbon materials have a more uniform porous structure, which is beneficial for the dispersion of silicon-based materials.

[0142] In some embodiments, the negative electrode active material further includes a coating layer located on at least a portion of the surface of the substrate material. The coating layer is located on the outer side of the negative electrode active material, thereby further preventing direct contact between the silicon-based material and the electrolyte, reducing the reactivity of the silicon-based material upon contact with air, thus reducing electrolyte side reactions, decreasing active ion consumption, and improving the cycle performance of the secondary battery. Furthermore, the coating layer can also buffer the volume expansion of the silicon-based material, which also helps improve the storage performance of the secondary battery.

[0143] In some embodiments, the coating layer comprises one or more of carbon materials, conductive polymers, metal oxides, and metal sulfides.

[0144] In some embodiments, the carbon material includes one or more of hard carbon, soft carbon, graphene, carbon fiber, and carbon nanotubes.

[0145] In some embodiments, the conductive polymer includes one or more of polyaniline, polypyrrole, and polythiophene.

[0146] In some embodiments, the metal oxide includes one or more of iron oxide, zinc oxide, tin oxide, copper oxide, and titanium oxide.

[0147] In some embodiments, the metal sulfide includes one or more of tin sulfide, molybdenum sulfide, titanium sulfide, iron sulfide, and copper sulfide.

[0148] In some embodiments, the coating layer comprises a carbon material, optionally including one or more of hard carbon, soft carbon, graphene, carbon fibers, and carbon nanotubes. Thus, in addition to preventing direct contact between the silicon-based material and the electrolyte and buffering the volume expansion of the silicon-based material, the coating layer can also contribute to the capacity and improve the specific capacity of the negative electrode active material. Furthermore, when the coating layer includes a carbon material, it also helps to improve the conductivity of the silicon-based material.

[0149] In some embodiments, the thickness of the coating layer is 0 nm-200 nm, optionally 10 nm-200 nm, 10 nm-180 nm, or 10 nm-150 nm. A coating layer thickness within these ranges is beneficial for the negative electrode active material to have high specific capacity and low volume expansion. In this application, when the coating layer thickness is 0 nm, it indicates that the negative electrode active material does not have a coating layer.

[0150] In some embodiments, the negative electrode active material includes carbon and silicon.

[0151] In some embodiments, the carbon content in the negative electrode active material is 40 wt%-60 wt%, for example, it can be any range consisting of 40 wt%, 42 wt%, 44 wt%, 46 wt%, 48 wt%, 50 wt%, 52 wt%, 54 wt%, 56 wt%, 58 wt%, 60 wt%, or more. Optionally, the carbon content in the negative electrode active material is 45 wt%-50 wt%.

[0152] In some embodiments, the silicon content in the negative electrode active material is 38 wt%-58 wt%, for example, it can be any range consisting of 40 wt%, 42 wt%, 44 wt%, 46 wt%, 48 wt%, 50 wt%, 52 wt%, 54 wt%, 56 wt%, 58 wt%, or higher. Optionally, the silicon content in the negative electrode active material is 40 wt%-55 wt%.

[0153] When the content of carbon and / or silicon in the negative electrode active material is within the above range, it is beneficial for the negative electrode active material to achieve both high specific capacity and high conductivity.

[0154] The carbon content in the negative electrode active material can be tested according to GB / T 20123-2006 / ISO 15350:2000, using an HCS-140 infrared carbon-sulfur analyzer. The silicon content in the negative electrode active material can be tested according to GB / T20975.5-2020.

[0155] In some embodiments, the negative electrode active material includes, in addition to carbon and silicon, other elements, including one or more of oxygen, metals, and nitrogen. The distribution area of ​​these other elements is not specifically limited; for example, they may be located in at least one of the coating layer, the silicon-based material, and the matrix material.

[0156] In some embodiments, optionally, the sum of the mass percentages of other elements in the negative electrode active material is 0wt%-20wt%, optionally 0wt%-10wt%, or 0wt%-5wt%. In this application, when the sum of the mass percentages of other elements in the negative electrode active material is 0wt%, it means that the negative electrode active material does not include elements other than carbon and silicon.

[0157] In some embodiments, the pore volume of the negative electrode active material is 0.001 cm³. 3 / g-0.02cm 3 / g, can be selected as 0.01cm 3 / g-0.02cm 3 / g. When the pore volume of the negative electrode active material is within the above range, the internal voids of the negative electrode active material are within a suitable range. On the one hand, this can improve the specific capacity and initial coulombic efficiency of the negative electrode active material, and on the other hand, it can buffer the stress generated during the expansion of silicon-based materials.

[0158] In this application, the pore volume of the negative electrode active material has a meaning known in the art and can be determined using instruments and methods known in the art. For example, it can be tested according to GB / T 21650.2-2008. The testing instrument can be a TRISTAR II 3020 specific surface area and porosity analyzer from Micromeritics, USA.

[0159] In some embodiments, the average particle size Dv50 of the negative electrode active material is 4 μm-12 μm. When the average particle size Dv50 of the negative electrode active material is within the above range, it helps to reduce surface activity, reduce interfacial side reactions, reduce SEI film formation consumption, and also helps to improve the active ion and electron transport performance, thereby further improving the cycle performance of the secondary battery.

[0160] In this application, the average particle size Dv50 of the negative electrode active material has a well-known meaning in the art, representing the particle size corresponding to a cumulative volume distribution percentage of 50%, which can be determined using instruments and methods known in the art. For example, it can be conveniently determined using a laser particle size analyzer, referring to GB / T 19077-2016. The testing instrument can be the Mastersizer 3000 laser particle size analyzer from Malvern Instruments Ltd., UK.

[0161] In some embodiments, the BET specific surface area of ​​the negative electrode active material is 1 m². 2 / g-15m 2 / g. When the BET specific surface area of ​​the negative electrode active material is within the above range, it helps to reduce surface activity, reduce interfacial side reactions, reduce SEI film formation consumption, and improve the first coulombic efficiency and cycle performance of the secondary battery.

[0162] In this application, the BET specific surface area of ​​the negative electrode active material has a meaning known in the art and can be measured using instruments and methods known in the art. For example, it can be measured using the nitrogen adsorption specific surface area analysis method according to GB / T 19587-2017, and calculated using the BET (Brunauer Emmett Teller) method. The nitrogen adsorption specific surface area analysis can be performed using a TRISTAR II 3020 specific surface area and porosity analyzer from Micromeritics, Inc., USA.

[0163] Preparation method

[0164] The second aspect of this application provides a method for preparing a negative electrode active material, which can prepare the negative electrode active material of the first aspect of this application.

[0165] The method includes the following steps: providing a matrix material comprising multiple pore structures; dispersing a silicon-based material into the pore structures of the matrix material to obtain a negative electrode active material, wherein the negative electrode active material comprises a matrix material and a silicon-based material, the matrix material comprising multiple pore structures, at least a portion of the silicon-based material being located within the pore structures of the matrix material, at least a portion of the silicon-based material being a crystalline structure, the silicon-based material comprising a first silicon-based material and a second silicon-based material with different grain sizes, and the ratio of the grain size of the first silicon-based material to the grain size of the second silicon-based material being greater than or equal to 1.6:1.

[0166] In some embodiments, the porosity of the substrate material is 30%-60%, optionally 40%-50%. A porosity within this range is beneficial for the smooth progress of the deposition process and also helps the negative electrode active material to have suitable silicon content, suitable specific surface area, and / or suitable pore volume. If the porosity of the substrate material is too low, some silicon-based material is easily deposited on the surface of the substrate material, affecting the initial coulombic efficiency of the negative electrode active material. If the porosity of the substrate material is too high, insufficient silicon-based material deposition can lead to an excessively large specific surface area of ​​the negative electrode active material, thereby increasing interfacial side reactions, increasing irreversible consumption of active ions, and reducing the initial coulombic efficiency of the negative electrode active material.

[0167] In some embodiments, the average particle size Dv50 of the substrate material is 4 μm-12 μm. When the average particle size Dv50 of the substrate material is within the above range, it is beneficial for the deposition process to proceed smoothly, and it is also beneficial for the negative electrode active material to have a suitable silicon content, a suitable specific surface area, and / or a suitable pore volume. When the average particle size Dv50 of the substrate material is too small, the deposition effect of the silicon-based material is poor, which is not conducive to subsequent two-stage deposition; when the average particle size Dv50 of the substrate material is too large, there is a risk of insufficient silicon-based material deposition, resulting in an excessively large specific surface area of ​​the negative electrode active material, which increases interfacial side reactions, increases irreversible consumption of active ions, and reduces the initial coulombic efficiency of the negative electrode active material.

[0168] In some embodiments, the matrix material includes carbon materials, which include one or more of graphite materials, activated carbon, biomass carbon, pyrolytic carbon, and resin carbon.

[0169] In this application, the matrix material can be obtained commercially or prepared according to methods known in the art, such as high-temperature pyrolysis of an organic carbon source or chemical activation treatment. The organic carbon source may include one or more of biomass materials and polymeric materials. The chemical activation treatment may be achieved by creating pores in the matrix material (e.g., carbon material) using a pore-forming agent (e.g., an alkaline solution).

[0170] In some embodiments, the step of dispersing silicon-based materials into the porous structure of the matrix material includes the following steps: placing the matrix material comprising multiple porous structures as a substrate in a reactor, introducing a first mixed gas containing silicon source gas and depositing at a first temperature T1 for a first time t1, and stopping the introduction of the first mixed gas after the deposition is completed; after the temperature inside the reactor drops to a second temperature T2, introducing a second mixed gas containing silicon source gas and depositing at the second temperature T2 for a second time t2, and obtaining the negative electrode active material after the deposition is completed. The region defined by the distance 0.5 times the length between any point on the outer surface of the negative electrode active material and the core of the particle extending from the outer surface of the particle to the inside of the particle is called the outer region, and the region inside the outer region is called the inner region. In the cross-sectional image of the negative electrode active material, the total cross-sectional area of ​​the first silicon-based material in the outer region is smaller than the total cross-sectional area of ​​the first silicon-based material in the inner region, and the total cross-sectional area of ​​the second silicon-based material in the inner region is smaller than the total cross-sectional area of ​​the second silicon-based material in the outer region.

[0171] In some embodiments, the process of dispersing silicon-based materials into the porous structure of the substrate material is a vapor deposition process. The vapor deposition process includes chemical vapor deposition and physical vapor deposition, and can be selected as chemical vapor deposition, such as any one of thermochemical vapor deposition, plasma-enhanced chemical vapor deposition, and microwave plasma-assisted chemical vapor deposition.

[0172] In some embodiments, the reactor includes, but is not limited to, any one of a deposition furnace, a rotary furnace, a tubular furnace, and a fluidized bed.

[0173] This application employs a two-stage vapor deposition process to deposit a first silicon-based material and a second silicon-based material in the porous structure of the substrate material in stages. Compared with conventional liquid phase deposition processes, vapor deposition facilitates better deposition and uniform dispersion of silicon-based materials in the porous structure of the substrate material, and avoids problems such as agglomeration of silicon-based materials and / or excessive deposition on the surface of the substrate material.

[0174] In some embodiments, before introducing the first mixed gas containing silicon source gas, the method further includes the steps of: placing a matrix material comprising a plurality of porous structures as a substrate in a reactor, and performing purging and preheating treatment using a protective gas, optionally, the preheating temperature being 200°C-300°C. This facilitates the removal of residual moisture in the matrix material, thereby facilitating the subsequent deposition of a first silicon-based material with a larger grain size.

[0175] In some embodiments, during the step of dispersing silicon-based materials into the porous structure of the matrix material, the volume percentage V1 of the silicon source gas in the first mixed gas is greater than the volume percentage V2 of the silicon source gas in the second mixed gas. This facilitates the adjustment of the distribution areas of the first and second silicon-based materials, ensuring that the first silicon-based material is mainly located in the internal region of the negative electrode active material, while the second silicon-based material is mainly located in the external region of the negative electrode active material. This allows for the full utilization of both the first silicon-based material's contribution to improving initial coulombic efficiency and the second silicon-based material's contribution to improving cycle performance and reducing volume expansion.

[0176] In some embodiments, during the step of dispersing silicon-based material into the porous structure of the matrix material, T1 > T2.

[0177] In some embodiments, during the step of dispersing the silicon-based material into the porous structure of the matrix material, t1 <t2。

[0178] In some embodiments, during the step of dispersing the silicon-based material into the porous structure of the matrix material, T1 > T2 and t1 <t2。

[0179] In the step of dispersing silicon-based materials into the porous structure of the matrix material, by adjusting the first temperature during deposition to be greater than the second temperature, it is beneficial to adjust the distribution areas of the first silicon-based material and the second silicon-based material. This allows the first silicon-based material to be mainly located in the internal region of the negative electrode active material, while the second silicon-based material is mainly located in the external region of the negative electrode active material. This fully leverages the role of the first silicon-based material in improving the initial coulombic efficiency, as well as the role of the second silicon-based material in improving cycle performance and reducing volume expansion.

[0180] By adjusting the first deposition time to be shorter than the second deposition time, it is beneficial to adjust the content and distribution area of ​​the first silicon-based material.

[0181] In some embodiments, after introducing a first mixed gas containing silicon source gas, the pressure inside the furnace can be adjusted to a slightly positive pressure, for example, 200 Pa to 600 Pa higher than atmospheric pressure, which is beneficial for the smooth progress of the deposition process.

[0182] In some embodiments, the first mixed gas includes a silicon source gas and a protective gas. Optionally, the volume percentage V1 of the silicon source gas in the first mixed gas is 10%-50%, for example, it can be any range consisting of 10%, 15%, 20%, 25%, 30%, 35%, 40%, 45%, 50% or more.

[0183] In some embodiments, the total gas flow rate of the first mixed gas is 0.5 L / min to 20 L / min. For example, it can be 1 L / min, 2 L / min, 3 L / min, 4 L / min, 5 L / min, 6 L / min, 7 L / min, 8 L / min, 9 L / min, 10 L / min, 12 L / min, 14 L / min, 16 L / min, 18 L / min, 20 L / min, or any range of the above values.

[0184] In some embodiments, the first temperature T1 is 500°C-700°C, for example, it can be a range consisting of any value of 520°C, 540°C, 560°C, 580°C, 600°C, 620°C, 640°C, 660°C, 680°C, 700°C or above.

[0185] In some embodiments, the first time t1 is 0.5h-8h, for example, it can be a range of 1h, 2h, 3h, 4h, 5h, 6h, 7h, 8h or any of the above values. Optionally, the first time t1 is 0.5h-4h.

[0186] By adjusting at least one of the composition ratio of the first mixed gas, the total gas flow rate of the first mixed gas, the first temperature, and the first time to be within the above range, it is beneficial to form a first silicon-based material with a larger grain size, and it is also beneficial to adjust parameters such as the distribution area and deposition amount of the first silicon-based material.

[0187] When the volume percentage of silicon source gas in the first mixed gas is too high and / or the total gas flow rate of the first mixed gas is too large, the content and distribution area of ​​the first silicon-based material increase, which is detrimental to the improvement of the cycle performance and storage performance of the secondary battery. When the volume percentage of silicon source gas in the first mixed gas is too low and / or the total gas flow rate of the first mixed gas is too small, the deposition amount of the first silicon-based material may be insufficient, which is detrimental to the improvement of the initial coulombic efficiency of the secondary battery. When the first temperature is too low, it is not conducive to the formation of first silicon-based material with a larger grain size, which is detrimental to the improvement of the initial coulombic efficiency of the secondary battery. When the first temperature is too high, the grain size of the silicon-based material increases, which is detrimental to the improvement of the cycle performance and storage performance of the secondary battery. When the first time is too short, the deposition amount of the first silicon-based material may be insufficient, which is detrimental to the improvement of the initial coulombic efficiency of the secondary battery. When the first time is too long, the content and distribution area of ​​the first silicon-based material increase, which is detrimental to the improvement of the cycle performance and storage performance of the secondary battery.

[0188] In some embodiments, after introducing a second mixed gas containing silicon source gas, the pressure inside the furnace can be adjusted to a slightly positive pressure, for example, 200 Pa to 600 Pa higher than atmospheric pressure, which is beneficial for the smooth progress of the deposition process.

[0189] In some embodiments, the second mixed gas includes a silicon source gas and a protective gas. Optionally, the volume percentage V2 of the silicon source gas in the second mixed gas is 10%-25%, for example, it can be any range consisting of 10%, 12%, 14%, 16%, 18%, 20%, 22%, 24% or more.

[0190] In some embodiments, the total gas flow rate of the second mixture is 0.5 L / min to 20 L / min. For example, it can be 1 L / min, 2 L / min, 3 L / min, 4 L / min, 5 L / min, 6 L / min, 7 L / min, 8 L / min, 9 L / min, 10 L / min, 12 L / min, 14 L / min, 16 L / min, 18 L / min, 20 L / min, or any range of the above values.

[0191] In some embodiments, the second temperature T2 is 500°C-600°C, for example, it can be a range consisting of any value of 500°C, 510°C, 520°C, 530°C, 540°C, 550°C, 560°C, 570°C, 580°C, 590°C, 600°C or above.

[0192] In some embodiments, the second time t2 is 4h-20h, for example, it can be a range of 4h, 5h, 6h, 7h, 8h, 9h, 10h, 11h, 12h, 13h, 14h, 15h, 16h, 18h, 20h or any of the above values. Optionally, the second time t2 is 4h-16h.

[0193] By adjusting at least one of the composition ratio of the second mixed gas, the total gas flow rate of the second mixed gas, the second temperature, and the second time to be within the above range, it is beneficial to form a second silicon-based material with a smaller grain size, and it is also beneficial to adjust parameters such as the distribution area and deposition amount of the second silicon-based material.

[0194] When the volume percentage of silicon source gas in the second mixed gas is too high and / or the total gas flow rate of the second mixed gas is too large, the second silicon-based material may be deposited on the surface of the substrate material, which may increase the difficulty of preparing the negative electrode slurry, and may also increase interfacial side reactions and irreversible consumption of active ions. Conversely, if the volume percentage of silicon source gas in the second mixed gas is too low and / or the total gas flow rate of the second mixed gas is too small, the deposition amount of the second silicon-based material may be insufficient, resulting in a larger specific surface area of ​​the negative electrode active material, increased interfacial side reactions, increased irreversible consumption of active ions, and a decrease in the initial coulombic efficiency. Furthermore, excessively low temperatures are unfavorable. The second silicon-based material is formed in a crystalline state. If the second temperature is too high, silicon-based materials with large grain sizes are easily formed in the outer region of the substrate material, which is not conducive to improving the first coulombic efficiency of the secondary battery. If the second time is too short, the deposition amount of the second silicon-based material may be insufficient, resulting in a large specific surface area of ​​the negative electrode active material, increased interfacial side reactions, increased irreversible consumption of active ions, and reduced first coulombic efficiency. If the second time is too long, the second silicon-based material may be deposited on the surface of the substrate material, which may increase the difficulty of preparing the negative electrode slurry, and may also increase interfacial side reactions and irreversible consumption of active ions.

[0195] In some embodiments, the total gas flow rate of the second mixture may be the same as the total gas flow rate of the first mixture.

[0196] In some embodiments, the method further includes the step of forming a coating layer on at least the surface of the obtained negative electrode active material, the coating layer comprising one or more of carbon materials, conductive polymers, metal oxides and metal sulfides.

[0197] The method of forming a coating layer on at least the surface of the obtained negative electrode active material is not specifically limited and can be selected according to the composition of the coating layer, for example, any one of solid phase coating, liquid phase coating or gas phase coating can be used.

[0198] In some embodiments, the step of forming the coating layer includes the following steps: mixing the obtained negative electrode active material with the coating material and then performing a carbonization treatment. Optionally, the coating material includes one or more of asphalt (e.g., coal tar pitch, petroleum asphalt, etc.) and polymer materials. Optionally, the carbonization treatment temperature is 500℃-1000℃.

[0199] In some embodiments, the step of forming the coating layer includes the following steps: placing the obtained negative electrode active material in a reactor, introducing a third mixed gas containing a carbon source gas, and depositing it at a third temperature T3 for a third time t3 to obtain a carbon-coated negative electrode active material. This facilitates the formation of a uniform carbon layer.

[0200] In some embodiments, the third mixture includes a carbon source gas and a protective gas. Optionally, the volume percentage V3 of the carbon source gas in the third mixture is 10%-50%, for example, it can be any range consisting of 10%, 15%, 20%, 25%, 30%, 35%, 40%, 45%, 50% or more.

[0201] In some embodiments, the total gas flow rate of the third mixture is 0.5 L / min to 20 L / min. For example, it can be 1 L / min, 2 L / min, 3 L / min, 4 L / min, 5 L / min, 6 L / min, 7 L / min, 8 L / min, 9 L / min, 10 L / min, 12 L / min, 14 L / min, 16 L / min, 18 L / min, 20 L / min, or any range of the above values.

[0202] In some embodiments, the third temperature T3 is 600°C-800°C, for example, it can be a range consisting of 600°C, 610°C, 620°C, 630°C, 640°C, 650°C, 660°C, 670°C, 680°C, 690°C, 700°C, 710°C, 720°C, 730°C, 740°C, 750°C, 760°C, 770°C, 780°C, 790°C, 800°C or any value above.

[0203] In some embodiments, the third time t3 is 0.5h-4h, for example, it can be a range consisting of 0.5h, 1h, 1.5h, 2h, 2.5h, 3h, 3.5h, 4h or any of the above values.

[0204] By adjusting at least one of the composition ratio of the third mixed gas, the total gas flow rate of the third mixed gas, the third temperature, and the third time to be within the above range, it is beneficial to form a coating layer of appropriate thickness and avoid the coating layer being too thick, which would reduce the initial coulombic efficiency and / or specific capacity of the negative electrode active material.

[0205] In this application, the term "protective gas" includes nitrogen and rare gases, which may include one or more of argon, helium, etc.

[0206] In this application, the term "silicon source gas" refers to a gas capable of forming the silicon-based material of this application. Optionally, the silicon source gas includes, but is not limited to, silane (H4Si), silane (H6Si2), propane (H8Si3), silicon tetrachloride (Cl4Si), trichlorosilane (Cl3HSi), dichlorosilane (Cl2H2Si), chlorosilane (ClH3Si), silicon tetrafluoride (F4Si), trifluorosilane (F3HSi), difluorosilane (F2H2Si), fluorosilane (FH3Si), hexachlorodisilane (Cl6Si2), pentachlorodisilane (Cl5HSi2), tetrachlorodisilane (Cl4H2Si2, including 1,1,2,2-tetrachlorodisilane and 1,1,1,2-tetrachlorodisilane), trichlorodisilane (Cl3H3Si2, including 1,1,2-trichlorodisilane and 1,1,2-tetrachlorodisilane), and trichlorodisilane (Cl3H3Si2, including 1,1,2-trichlorodisilane and 1,1,2-tetrachlorodisilane). 1-Trichlorodisilane), dichlorodisilane (Cl2H4Si2, including 1,1-dichlorodisilane and 1,2-dichlorodisilane), monochlorodisilane (ClH5Si2), hexafluorodisilane (F6Si2), pentafluorodisilane (F5HSi2), 1,1,2,2-tetrafluorodisilane (F4H2Si2), 1,1,1-trifluorodisilane (F3H3Si2), difluorodisilane (F2H4) Si2 includes one or more of 1,1-difluorodisilane, 1,2-difluorodisilane, monofluorodisilane (FH5Si2), methylsilane, ethylsilane, dimethylsilane, trimethylsilane, tetramethylsilane, methyldisilane, dimethyldisilane, trimethyldisilane, tetramethyldisilane, hexamethylsilane, methyltrichlorosilane, methylchlorosilane, chloroethylsilane, dichlorodimethylsilane, and dichlorodiethylsilane.

[0207] In this application, "carbon source gas" refers to a gas capable of forming carbon materials. Optionally, the carbon source gas includes, but is not limited to, one or more of the following: methane, ethane, propane, isopropane, butane, isobutane, ethylene, propylene, butene, acetylene, chloroethane, fluoroethane, difluoroethane, chloromethane, fluoromethane, difluoromethane, trifluoromethane, vinyl chloride, vinyl fluoride, difluoroethylene, methylamine, formaldehyde, benzene, toluene, xylene, styrene, and phenol.

[0208] Unless otherwise specified, all raw materials and instruments used in the preparation method of this application can be obtained commercially.

[0209] Secondary batteries

[0210] The third aspect of this application provides a secondary battery.

[0211] The secondary battery mentioned in the embodiments or implementations of this application refers to a single physical module comprising one or more battery cells to provide higher voltage and capacity. For example, the secondary battery mentioned in this application may include battery cells, battery modules, or battery packs. A battery cell is the smallest unit constituting a secondary battery, capable of charging and discharging independently. This application does not impose any particular limitation on the shape of the battery cell; it can be cylindrical, square, or any other arbitrary shape. Figure 2 The example shown is a square-structured battery cell 5.

[0212] In some embodiments, a single battery cell includes an electrode assembly and an electrolyte, and the single battery cell may also include an outer packaging. The electrode assembly is made from a positive electrode, a negative electrode, and a separator, etc., by a winding process and / or a stacking process, and the outer packaging is used to encapsulate the electrode assembly. The outer packaging can be a rigid shell, such as a hard plastic shell, an aluminum shell, a steel shell, etc. The outer packaging can also be a flexible package, such as a pouch. The material of the flexible package can be plastic, such as one or more of polypropylene (PP), polybutylene terephthalate (PBT), and polybutylene succinate (PBS).

[0213] In some embodiments, such as Figure 3 As shown, the outer packaging may include a housing 51 and a cover 53. The housing 51 may include a base plate and side plates connected to the base plate, the base plate and side plates enclosing a receiving cavity. The housing 51 has an opening communicating with the receiving cavity, and the cover 53 is used to cover the opening to close the receiving cavity. Electrode assemblies 52 are encapsulated in the receiving cavity. The number of electrode assemblies 52 contained in the battery cell 5 may be one or more, and can be adjusted as needed.

[0214] In some embodiments of this application, individual battery cells can be assembled into a battery module. The number of individual battery cells contained in a battery module can be multiple, and the specific number can be adjusted according to the application and capacity of the battery module. Figure 3 This is a schematic diagram of battery module 4 as an example. Figure 4 As shown, in battery module 4, multiple battery cells 5 can be arranged sequentially along the length of battery module 4. Of course, they can also be arranged in any other manner. Furthermore, these multiple battery cells 5 can be fixed in place using fasteners.

[0215] Optionally, the battery module 4 may also include a housing with a receiving space in which multiple battery cells 5 are received.

[0216] In some embodiments, the battery modules described above can also be assembled into a battery pack, and the number of battery modules contained in the battery pack can be adjusted according to the application and capacity of the battery pack. Figure 5 and Figure 6 This is a schematic diagram of battery pack 1 as an example. Figure 5 and Figure 6 As shown, the battery pack 1 may include a battery box and multiple battery modules 4 disposed within the battery box. The battery box includes an upper body 2 and a lower body 3. The upper body 2 covers the lower body 3, forming a closed space for accommodating the battery modules 4. The multiple battery modules 4 can be arranged in any manner within the battery box.

[0217] This application does not impose any particular restrictions on the type of secondary battery. For example, secondary batteries may include, but are not limited to, lithium-ion batteries, sodium-ion batteries, etc.

[0218] [Negative electrode plate]

[0219] In some embodiments, the negative electrode sheet includes a negative current collector and a negative electrode film layer disposed on at least one surface of the negative current collector and comprising a negative electrode active material. For example, the negative current collector has two surfaces opposite each other in its thickness direction, and the negative electrode film layer is disposed on either or both of the two opposite surfaces of the negative current collector.

[0220] In some embodiments, the negative electrode film layer comprises the negative electrode active material of the first aspect of the present application or the negative electrode active material prepared by the preparation method described in the second aspect of the present application. This enables the secondary battery to achieve high energy density, high initial coulombic efficiency, long cycle life, and long storage life.

[0221] In some embodiments, the negative electrode film layer may further include other negative electrode active materials besides the aforementioned negative electrode active materials. In some embodiments, the other negative electrode active materials include, but are not limited to, one or more of natural graphite, artificial graphite, soft carbon, hard carbon, elemental silicon, silicon oxide, silicon-nitrogen composites, silicon alloys, elemental tin, tin oxides, tin alloys, and lithium titanate. This application is not limited to these materials, and other conventionally known materials that can be used as negative electrode active materials for secondary batteries may also be used.

[0222] In some embodiments, the negative electrode film layer may optionally include a negative electrode conductive agent. This application does not impose any particular limitation on the type of negative electrode conductive agent. As an example, the negative electrode conductive agent may include one or more of superconducting carbon, conductive graphite, acetylene black, carbon black, Ketjen black, carbon dots, carbon nanotubes, graphene, and carbon nanofibers.

[0223] In some embodiments, the negative electrode film layer may optionally include a negative electrode binder. This application does not impose any particular limitation on the type of negative electrode binder. As an example, the negative electrode binder may include one or more of the following: styrene-butadiene rubber (SBR), water-soluble unsaturated resin SR-1B, waterborne acrylic resins (e.g., polyacrylic acid PAA, polymethacrylic acid PMAA, sodium polyacrylate PAAS), polyacrylamide (PAM), polyvinyl alcohol (PVA), sodium alginate (SA), and carboxymethyl chitosan (CMCS).

[0224] In some embodiments, the negative electrode film may optionally include other additives. As an example, other additives may include thickeners, such as sodium carboxymethyl cellulose (CMC), PTC thermistor materials, etc.

[0225] In some embodiments, the negative electrode current collector may be a metal foil or a composite current collector. As an example of the metal foil, copper foil may be used. The composite current collector may include a polymeric material substrate and a metal material layer formed on at least one surface of the polymeric material substrate. As an example, the metal material may include one or more of copper, copper alloys, nickel, nickel alloys, titanium, titanium alloys, silver, and silver alloys. As an example, the polymeric material substrate may include one or more of polypropylene (PP), polyethylene terephthalate (PET), polybutylene terephthalate (PBT), polystyrene (PS), and polyethylene (PE).

[0226] The negative electrode film layer is typically formed by coating a negative electrode slurry onto a negative electrode current collector, followed by drying and cold pressing. The negative electrode slurry is typically formed by dispersing a negative electrode active material, optional conductive agent, optional binder, and other optional additives in a solvent and stirring until homogeneous. The solvent can be N-methylpyrrolidone (NMP) or deionized water, but is not limited to these.

[0227] The negative electrode sheet does not exclude other additional functional layers besides the negative electrode film layer. For example, in some embodiments, the negative electrode sheet of this application may further include a conductive undercoat layer (e.g., composed of a conductive agent and an adhesive) sandwiched between the negative electrode current collector and the negative electrode film layer and disposed on the surface of the negative electrode current collector; in some embodiments, the negative electrode sheet of this application may further include a protective layer covering the surface of the negative electrode film layer.

[0228] [Positive electrode plate]

[0229] In some embodiments, the positive electrode includes a positive current collector and a positive electrode film layer disposed on at least one surface of the positive current collector and comprising a positive electrode active material. For example, the positive current collector has two surfaces opposite each other in its thickness direction, and the positive electrode film layer is disposed on either or both of the two opposite surfaces of the positive current collector.

[0230] The positive electrode film layer includes a positive electrode active material, which may be a positive electrode active material known in the art for use in secondary batteries.

[0231] When the secondary battery of this application is a lithium-ion battery, the positive electrode active material may include one or more of lithium transition metal oxides, lithium-containing phosphates with an olivine structure, and their respective modified compounds. Examples of lithium transition metal oxides may include one or more of lithium cobalt oxides, lithium nickel oxides, lithium manganese oxides, lithium nickel cobalt oxides, lithium manganese cobalt oxides, lithium nickel manganese oxides, lithium nickel cobalt manganese oxides, lithium nickel cobalt aluminum oxides, and their respective modified compounds. Examples of lithium-containing phosphates with an olivine structure may include one or more of lithium iron phosphate, lithium iron phosphate and carbon composites, lithium manganese phosphate, lithium manganese phosphate and carbon composites, lithium manganese iron phosphate, lithium manganese iron phosphate and carbon composites, and their respective modified compounds. This application is not limited to these materials, and other conventionally known materials that can be used as positive electrode active materials for secondary batteries may also be used.

[0232] In some embodiments, to further improve the energy density of secondary batteries, the positive electrode active material for lithium-ion batteries may include materials with the general formula Li. a Ni b Co c M d O e A f One or more of lithium transition metal oxides and their modified compounds. 0.8≤a≤1.2, 0.5≤b<1, 0<c<1, 0<d<1, 1≤e≤2, 0≤f≤1, M includes one or more selected from Mn, Al, Zr, Zn, Cu, Cr, Mg, Fe, V, Ti and B, and A includes one or more selected from N, F, S and Cl.

[0233] As an example, positive electrode active materials for lithium-ion batteries may include LiCoO2, LiNiO2, LiMnO2, LiMn2O4, and LiNi 1 / 3 Co 1 / 3 Mn 1 / 3 O2(NCM333), LiNi 0.5 Co 0.2 Mn 0.3 O2(NCM523), LiNi 0.6 Co0.2 Mn 0.2 O2(NCM622), LiNi 0.8 Co 0.1 Mn 0.1 O2(NCM811), LiNi 0.85 Co 0.15 Al 0.05 One or more of O2, LiFePO4 and LiMnPO4.

[0234] When the secondary battery of this application is a sodium-ion battery, the positive electrode active material may include, but is not limited to, one or more of sodium-containing transition metal oxides, polyanionic materials (such as phosphates, fluorophosphates, pyrophosphates, sulfates, etc.), and Prussian blue materials.

[0235] As an example, positive electrode active materials for sodium-ion batteries may include NaFeO2, NaCoO2, NaCrO2, NaMnO2, NaNiO2, and NaNi 1 / 2 Ti 1 / 2 O2, NaNi 1 / 2 Mn 1 / 2 O2, Na 2 / 3 Fe 1 / 3 Mn 2 / 3 O2, NaNi 1 / 3 Co 1 / 3 Mn 1 / 3 O2, NaFePO4, NaMnPO4, NaCoPO4, Prussian blue materials and materials with the general formula X p M' q (PO4) r O x Y 3-x One or more of the materials. In general formula X p M' q (PO4) r O x Y 3-x In the given condition, 0 < p ≤ 4, 0 < q ≤ 2, 1 ≤ r ≤ 3, 0 ≤ x ≤ 2, and X includes elements selected from H. + Li + Na + K + and NH4 + One or more of the following, M' is a transition metal cation, which may be selected from one or more of V, Ti, Mn, Fe, Co, Ni, Cu and Zn, and Y is a halide anion, which may be selected from one or more of F, Cl and Br.

[0236] In this application, the modified compounds of the above-mentioned positive electrode active materials may be those that have undergone doping modification and / or surface coating modification of the positive electrode active materials.

[0237] In some embodiments, the positive electrode film may optionally include a positive electrode conductive agent. This application does not impose any particular limitation on the type of positive electrode conductive agent. As an example, the positive electrode conductive agent includes one or more of superconducting carbon, conductive graphite, acetylene black, carbon black, Ketjen black, carbon dots, carbon nanotubes, graphene, and carbon nanofibers.

[0238] In some embodiments, the positive electrode film layer may optionally include a positive electrode binder. This application does not impose any particular limitation on the type of positive electrode binder. As an example, the positive electrode binder may include one or more of polyvinylidene fluoride (PVDF), polytetrafluoroethylene (PTFE), PVDF-tetrafluoroethylene-propylene terpolymer, PVDF-hexafluoropropylene-tetrafluoroethylene terpolymer, tetrafluoroethylene-hexafluoropropylene copolymer, and fluorinated acrylate resins.

[0239] In some embodiments, the positive current collector may be a metal foil or a composite current collector. An example of the metal foil is aluminum foil. The composite current collector may include a polymer base layer and a metal layer formed on at least one surface of the polymer base layer. An example of the metal material may be one or more of aluminum, aluminum alloys, nickel, nickel alloys, titanium, titanium alloys, silver, and silver alloys. An example of the polymer base layer may be one or more of polypropylene (PP), polyethylene terephthalate (PET), polybutylene terephthalate (PBT), polystyrene (PS), and polyethylene (PE).

[0240] The positive electrode film is typically formed by coating a positive electrode slurry onto a positive electrode current collector, followed by drying and cold pressing. The positive electrode slurry is typically formed by dispersing the positive electrode active material, optional conductive agent, optional binder, and any other components in a solvent and stirring until homogeneous. The solvent may be N-methylpyrrolidone (NMP), but is not limited to this.

[0241] [Electrolytes]

[0242] The electrolyte acts as a conductor of active ions between the positive and negative electrode plates. This application does not impose specific limitations on the type of electrolyte; it can be selected according to requirements. For example, the electrolyte may include one or more selected from solid electrolytes and liquid electrolytes (i.e., electrolyte solutions).

[0243] In some embodiments, the electrolyte is an electrolyte solution comprising an electrolyte salt and a solvent.

[0244] When the secondary battery of this application is a lithium-ion battery, as an example, the electrolyte salt may include one or more of lithium hexafluorophosphate (LiPF6), lithium tetrafluoroborate (LiBF4), lithium perchlorate (LiClO4), lithium hexafluoroarsenate (LiAsF6), lithium bis(fluorosulfonyl)imide (LiFSI), lithium bis(trifluoromethanesulfonyl)imide (LiTFSI), lithium trifluoromethanesulfonate (LiTFS), lithium difluorooxalate borate (LiDFOB), lithium dioxalate borate (LiBOB), lithium difluorophosphate (LiPO2F2), lithium difluorodioxalate phosphate (LiDFOP), and lithium tetrafluorooxalate phosphate (LiTFOP).

[0245] When the secondary battery of this application is a sodium-ion battery, particularly a sodium-ion secondary battery, the electrolyte salt may include one or more of the following: sodium hexafluorophosphate (NaPF6), sodium tetrafluoroborate (NaBF4), sodium perchlorate (NaClO4), sodium hexafluoroarsenate (NaAsF6), sodium bis(fluorosulfonyl)imide (NaFSI), sodium bis(trifluoromethanesulfonyl)imide (NaTFSI), sodium trifluoromethanesulfonate (NaTFS), sodium difluorooxalate borate (NaDFOB), sodium dioxalate borate (NaBOB), sodium difluorophosphate (NaPO2F2), sodium difluorodioxalate phosphate (NaDFOP), and sodium tetrafluorooxalate phosphate (NaTFOP).

[0246] The type of solvent is not specifically limited and can be selected according to actual needs. In some embodiments, as an example, the solvent may include one or more of the following: ethylene carbonate (EC), propylene carbonate (PC), ethyl methyl carbonate (EMC), diethyl carbonate (DEC), dimethyl carbonate (DMC), dipropyl carbonate (DPC), methyl propyl carbonate (MPC), ethyl propyl carbonate (EPC), butyl carbonate (BC), fluoroethylene carbonate (FEC), methyl formate (MF), methyl acetate (MA), ethyl acetate (EA), propyl acetate (PA), methyl propionate (MP), ethyl propionate (EP), propyl propionate (PP), methyl butyrate (MB), ethyl butyrate (EB), 1,4-butyrolactone (GBL), sulfolane (SF), dimethyl sulfone (MSM), methyl ethyl sulfone (EMS), and diethyl sulfone (ESE).

[0247] In some embodiments, the electrolyte may optionally include additives. For example, the additives may include negative electrode film-forming additives, positive electrode film-forming additives, and additives that can improve certain battery performance, such as additives that improve battery overcharge performance, additives that improve battery high-temperature performance, and additives that improve battery low-temperature power performance.

[0248] [Isolation membrane]

[0249] Secondary batteries using electrolytes, as well as some secondary batteries using solid electrolytes, also include a separator. The separator is disposed between the positive and negative electrodes, primarily serving to prevent short circuits between the positive and negative electrodes while allowing active ions to pass through. This application does not impose any particular limitation on the type of separator; any known porous separator with good chemical and mechanical stability can be selected.

[0250] In some embodiments, the material of the separator may include one or more of glass fiber, nonwoven fabric, polyethylene, polypropylene, and polyvinylidene fluoride. The separator may be a single-layer film or a multi-layer composite film. When the separator is a multi-layer composite film, the materials of each layer may be the same or different.

[0251] [Preparation Method]

[0252] The method for preparing the secondary battery described in this application is well known. In some embodiments, a positive electrode, a separator, a negative electrode, and an electrolyte can be assembled to form a secondary battery. As an example, the positive electrode, separator, and negative electrode can be formed into an electrode assembly through a winding process and / or a stacking process. The electrode assembly is placed in an outer packaging, dried, and then injected with an electrolyte. After vacuum sealing, settling, formation, and shaping processes, a battery cell is obtained. Multiple battery cells can be further connected in series, parallel, or a combination thereof to form a battery module. Multiple battery modules can also be connected in series, parallel, or a combination thereof to form a battery pack. In some embodiments, multiple battery cells can also be directly assembled into a battery pack.

[0253] Electrical appliances

[0254] This application also provides an electrical device, which includes the secondary battery described in this application. The secondary battery can be used as a power source for the electrical device or as an energy storage unit. The electrical device can be, but is not limited to, mobile devices (e.g., mobile phones, tablets, laptops, etc.), electric vehicles (e.g., pure electric vehicles, hybrid electric vehicles, plug-in hybrid electric vehicles, electric bicycles, electric scooters, electric golf carts, electric trucks, etc.), electric trains, ships and satellites, energy storage systems, etc.

[0255] The electrical device can select the specific type of secondary battery according to its usage requirements, such as a battery cell, battery module, or battery pack.

[0256] Figure 7 This is a schematic diagram illustrating an example of an electrical device. This device could be a pure electric vehicle, a hybrid electric vehicle, or a plug-in hybrid electric vehicle, etc. To meet the device's requirements for high power and high energy density, a battery pack or battery module can be used as the power source.

[0257] Another example of an electrical device could be a mobile phone, tablet, or laptop. These devices typically require a slim and lightweight design and can use a single battery cell as their power source.

[0258] Example

[0259] The following embodiments describe the disclosure of this application in more detail. These embodiments are merely illustrative, as various modifications and variations will be apparent to those skilled in the art within the scope of the disclosure of this application. Unless otherwise stated, all parts, percentages, and ratios reported in the following embodiments are based on mass, and all reagents used in the embodiments are commercially available or synthesized by conventional methods and can be used directly without further processing, and the instruments used in the embodiments are commercially available.

[0260] Example 1

[0261] (1) Preparation of negative electrode active materials

[0262] One kilogram of commercially available porous biomass carbon with a porosity of 45% was selected as the substrate and placed in a vapor deposition furnace. The furnace was kept at a rotation speed of 0.5 rpm and purged with argon gas. The temperature was then preheated to 200°C. The temperature was further increased to 600°C, and a first gas mixture of 30% silane and 70% argon (volume ratio) was introduced at a total gas flow rate of 2 L / min. The furnace pressure was a slightly positive pressure 400 Pa higher than atmospheric pressure, and the deposition time was 4 hours. The introduction of the first gas mixture was then stopped, and the furnace temperature was allowed to drop to 550°C. A second gas mixture of 15% silane and 85% argon (volume ratio) was then introduced at a total gas flow rate of 2 L / min, and the deposition time was 12 hours. The second mixed gas was shut off, the temperature was raised again to 700℃, and the third mixed gas was introduced with 20% acetylene + 80% argon (volume ratio). The total gas flow rate was 2L / min, the deposition time was 1h, and after the deposition was completed, the material was cooled, discharged, and passed through a 325-mesh sieve to obtain the negative electrode active material.

[0263] (2) Preparation of secondary batteries (full cells)

[0264] Preparation of negative electrode sheet: The negative electrode active material prepared above is mixed with conductive agent conductive carbon black and carbon nanotubes and binder polyacrylic acid at a mass ratio of 95:1.9:0.1:3. The mixture is then added to deionized water as a solvent and stirred under the action of a high-speed stirrer until the system is homogeneous, thereby obtaining a negative electrode slurry with a solid content of 45%. The negative electrode slurry is uniformly coated on the negative electrode current collector copper foil and dried at 85°C. After cold pressing, the negative electrode sheet is obtained.

[0265] Preparation of the positive electrode: The positive electrode active material LiNi... 0.8Co 0.1 Mn 0.1 O2 (NCM811), conductive agent carbon black (Super P), and binder polyvinylidene fluoride (PVDF) are mixed thoroughly in an appropriate amount of solvent NMP at a mass ratio of 97:1:2 to form a uniform positive electrode slurry. The positive electrode slurry is then uniformly coated onto the surface of the positive electrode current collector aluminum foil, and after drying and cold pressing, a positive electrode sheet is obtained.

[0266] Preparation of electrolyte: Ethylene carbonate (EC), ethyl methyl carbonate (EMC), and diethyl carbonate (DEC) were mixed uniformly in a volume ratio of 20:20:60 as an organic solvent. LiPF6 was then dissolved in the organic solvent, and fluoroethylene carbonate (FEC) was added. The concentration of LiPF6 in the electrolyte was 1 mol / L, and the mass percentage of FEC was 5 wt%.

[0267] Preparation of the separator membrane: Celgard 2400 separator membrane was used.

[0268] Preparation of secondary batteries: The positive electrode, separator, and negative electrode are stacked and wound in sequence to obtain an electrode assembly; the electrode assembly is placed in an outer packaging, dried, and then injected with electrolyte. After vacuum sealing, standing, formation, and shaping, a secondary battery is obtained.

[0269] (3) Preparation of button cell (half cell)

[0270] The prepared negative electrode active material was mixed with conductive carbon black (conductive agent) and polyacrylic acid (binder) at a mass ratio of 8:1:1. The mixture was then added to deionized water and stirred under high speed until homogeneous, yielding a negative electrode slurry with a solid content of 45%. This slurry was uniformly coated onto a copper foil current collector and dried at 85°C. After cold pressing, the electrode sheet was obtained. A lithium metal sheet was used as the counter electrode, a Celgard 2400 separator was employed, and the same electrolyte as used in the secondary battery preparation was injected to assemble a coin cell.

[0271] Example 2-20

[0272] The preparation methods for secondary batteries and coin cells are similar to those in Example 1, except that the preparation process parameters of the negative electrode active material are adjusted, as detailed in Table 1.

[0273] Example 21

[0274] The preparation methods for secondary batteries and coin cells are similar to those in Example 1, except that the preparation process parameters of the negative electrode active material are adjusted.

[0275] One kilogram of commercially available porous biomass carbon with a porosity of 45% was selected as the substrate and placed in a vapor deposition furnace. The furnace rotation speed was maintained at 0.5 rpm, and argon gas was used for purging. The temperature was preheated to 200°C. The temperature was then increased to 550°C, and a first gas mixture of 15% silane and 85% argon (volume ratio) was introduced at a total gas flow rate of 2 L / min. The furnace pressure was a slightly positive pressure 400 Pa higher than atmospheric pressure, and the deposition time was 12 hours. The first gas mixture was then stopped, and the furnace temperature was increased to 600°C. A second gas mixture of 30% silane and 70% argon (volume ratio) was introduced at a total gas flow rate of 2 L / min, and the deposition time was 4 hours. The second mixed gas was shut off, the temperature was raised again to 700℃, and the third mixed gas was introduced with 20% acetylene + 80% argon (volume ratio). The total gas flow rate was 2L / min, the deposition time was 1h, and after the deposition was completed, the material was cooled, discharged, and passed through a 325-mesh sieve to obtain the negative electrode active material.

[0276] Comparative Example 1

[0277] The preparation methods for secondary batteries and coin cells are similar to those in Example 1, except that the preparation process parameters of the negative electrode active material are adjusted.

[0278] Amorphous carbon-coated crystalline silicon is used as the negative electrode active material, with a coating thickness of 300 nm.

[0279] Comparative Example 2

[0280] The preparation methods for secondary batteries and coin cells are similar to those in Example 1, except that the preparation process parameters of the negative electrode active material are adjusted.

[0281] One kilogram of commercially available porous biomass carbon with a porosity of 45% was selected as the substrate and placed in a vapor deposition furnace. The furnace rotation speed was maintained at 0.5 rpm, and argon gas was used for purging. The temperature was then preheated to 200°C. The temperature was further increased to 600°C, and a first mixed gas of 30% silane and 70% argon (volume ratio) was introduced at a total gas flow rate of 2 L / min. The furnace pressure was a slightly positive pressure 400 Pa higher than atmospheric pressure, and the deposition time was 12 hours. The first mixed gas was then turned off, and the temperature was raised again to 700°C. A second mixed gas of 20% acetylene and 80% argon (volume ratio) was introduced at a total gas flow rate of 2 L / min, and the deposition time was 1 hour. After deposition, the material was cooled, discharged, and sieved through a 325-mesh sieve to obtain the negative electrode active material.

[0282] Comparative Example 3

[0283] The preparation methods for secondary batteries and coin cells are similar to those in Example 1, except that the preparation process parameters of the negative electrode active material are adjusted.

[0284] One kilogram of commercially available porous biomass carbon with a porosity of 45% was selected as the substrate and placed in a vapor deposition furnace. The furnace rotation speed was maintained at 0.5 rpm, and argon gas was used for purging. The temperature was then preheated to 200°C. The temperature was further increased to 450°C, and a first mixed gas mixture of 15% silane and 85% argon (volume ratio) was introduced at a total gas flow rate of 2 L / min. The furnace pressure was a slightly positive pressure 400 Pa higher than atmospheric pressure, and the deposition time was 18 hours. The first mixed gas mixture was then turned off, and the temperature was raised again to 700°C. A second mixed gas mixture of 20% acetylene and 80% argon (volume ratio) was introduced at a total gas flow rate of 2 L / min, and the deposition time was 1 hour. After deposition, the material was cooled, discharged, and sieved through a 325-mesh sieve to obtain the negative electrode active material.

[0285] Table 1

[0286]

[0287]

[0288] Test section

[0289] (1) Grain size test

[0290] A dual-beam focused ion beam microscope (DBOM) was used to extract cross-sectional images of the negative electrode active material particles from their cores. Then, a high-resolution transmission electron microscope (HRTEM) was used to observe and calculate the grain size of the crystalline silicon-based material. In the acquired cross-sectional images, regions exhibiting lattice fringes were designated as grains, and the diameter of these regions was taken as the grain size. The average of at least 50 grain sizes was used as the test result. When testing the grain size of the first silicon-based material, samples were taken near the particle core; when testing the grain size of the second silicon-based material, samples were taken near the particle surface. The testing instruments used were the Thermo Fisher Scientific Helios 5CX dual-beam focused ion beam / scanning electron microscope system and the Thermo Fisher Scientific Spectra S / TEM scanning transmission electron microscope.

[0291] The grain area is calculated with the grain shape being spherical, and the diameter of the sphere is calculated using the grain size.

[0292] The region defined by the outer surface of the negative electrode active material particles extending into the particle from a distance of 0.5 times the length between any point on the outer surface of the particle and the particle core is called the outer region, and the region inside the outer region is called the inner region.

[0293] The ratio of the total cross-sectional area of ​​the first silicon-based material in the outer region to the total cross-sectional area of ​​the first silicon-based material in the inner region of the above cross-sectional image is denoted as α1. The ratio of the total cross-sectional area of ​​the second silicon-based material in the inner region to the total cross-sectional area of ​​the second silicon-based material in the outer region of the above cross-sectional image is denoted as α2. The ratio of the total cross-sectional area of ​​the first silicon-based material in the above cross-sectional image to the total cross-sectional area of ​​the negative electrode active material is denoted as γ1. The ratio of the total cross-sectional area of ​​the second silicon-based material in the above cross-sectional image to the total cross-sectional area of ​​the negative electrode active material is denoted as γ2.

[0294] (2) Element content test of negative electrode active material

[0295] The carbon content in the negative electrode active material is tested according to GB / T 20123-2006 / ISO 15350:2000. The testing instrument can be an HCS-140 infrared carbon-sulfur analyzer.

[0296] The silicon content in the negative electrode active material was tested according to GB / T 20975.5-2020.

[0297] (3) Test of average particle size Dv50 of negative electrode active material

[0298] Referring to GB / T 19077-2016, the volumetric particle size distribution curve of the negative electrode active material was obtained, and the particle size corresponding to the cumulative volume distribution percentage reaching 50% was taken as the average particle size Dv50. The testing instrument can be a Mastersizer 3000 laser particle size analyzer from Malvern Instruments Ltd., UK.

[0299] (4) Specific surface area test of negative electrode active material

[0300] Referring to GB / T 19587-2004, the nitrogen adsorption specific surface area analysis method was used for testing, and the specific surface area of ​​the negative electrode active material was calculated using the BET (Brunauer Emmett Teller) method. The testing instrument was a TRISTAR II 3020 specific surface area and porosity analyzer from Micromeritics, USA.

[0301] (5) Pore volume test of negative electrode active material

[0302] The pore volume of the negative electrode active material was tested according to GB / T 21650.2-2008. The testing instrument can be a TRISTAR II 3020 specific surface area and porosity analyzer from Micromeritics, USA.

[0303] (6) First Coulomb efficiency test

[0304] After the prepared coin cell was left to stand for 60 minutes, it was discharged at a constant current of 0.05C to 5mV, and then discharged at 50μA to 5mV. The total discharge capacity of the coin cell was recorded as the initial lithium intercalation capacity. After standing for 10 minutes, the coin cell was charged at a constant current of 0.1C to 0.8V. The charging capacity of the coin cell was recorded as the initial lithium deintercalation capacity.

[0305] The initial coulombic efficiency of the negative electrode active material = initial delithiation capacity / initial lithium insertion capacity.

[0306] (7) Cycle performance test of secondary batteries

[0307] At 25°C, the prepared secondary battery was fully charged at 0.5C and then fully discharged at 1C. This constitutes one charge-discharge cycle. The discharge capacity at this point is recorded as the initial discharge capacity. The secondary battery was then subjected to cyclic charge-discharge tests using the above method, and the discharge capacity after each cycle was recorded until the discharge capacity of the secondary battery decreased to 80% of the initial discharge capacity. The number of cycles at this point characterizes the cycle performance of the secondary battery. The higher the number of cycles, the better the cycle performance.

[0308] (8) Volume expansion test of negative electrode sheet

[0309] At 25°C, the prepared secondary battery was fully charged at 0.33C, and then disassembled in a drying room to obtain the negative electrode sheet. The thickness H1 of the negative electrode sheet under full charge was recorded. The volume expansion rate of the negative electrode sheet = (H1-H0) / H0, where H0 represents the initial thickness of the negative electrode sheet after cold pressing.

[0310]

[0311] Table 3

[0312] Example 1 15% 48% 3.1:100 6.5:100 Example 2 20% 43% 10:100 1.8:100 Example 3 25% 38% 40:100 0:100 Example 4 10% 53% 0:100 12:100 Example 5 5% 58% 0:100 25:100 Example 6 40% 25% 120:100 0:100 Example 21 15% 48% 100:0 57:100

[0313] Based on the test results in Table 2, it can be seen that by placing at least a portion of the silicon-based material within the porous structure of the matrix material, and by including a first silicon-based material with a larger grain size and a second silicon-based material with a smaller grain size, the negative electrode active material can achieve high capacity, high initial coulombic efficiency, and low volume expansion. Furthermore, the secondary battery can also achieve high energy density, high initial coulombic efficiency, long cycle life, and long storage life.

[0314] Based on the test results of Examples 1 and 21, it can be seen that by placing the first silicon-based material with a larger grain size mainly in the internal region of the negative electrode active material and the second silicon-based material with a smaller grain size mainly in the external region of the negative electrode active material, the first silicon-based material can fully play its role in improving the initial coulombic efficiency, while the second silicon-based material can fully play its role in improving cycle performance and reducing volume expansion. Thus, the secondary battery can better balance high energy density, high initial coulombic efficiency, long cycle life, and long storage life.

[0315] The test results in Table 2 also show that when the ratio γ1 of the total cross-sectional area of ​​the first silicon-based material to the total cross-sectional area of ​​the negative electrode active material is greater than 0 and less than or equal to 25%, and can be selected as 5%-20%, the secondary battery using the negative electrode active material can better balance high energy density, high initial coulombic efficiency, long cycle life and long storage life.

[0316] Based on the test results in Tables 2 and 3, it can be seen that when the negative electrode active material also satisfies the condition that the total cross-sectional area of ​​the first silicon-based material in the outer region is less than the total cross-sectional area of ​​the first silicon-based material in the inner region, and optionally, the ratio α1 of the total cross-sectional area of ​​the first silicon-based material in the outer region to the total cross-sectional area of ​​the first silicon-based material in the inner region is (0-50):100, or more preferably (0-10):100, the secondary battery using the aforementioned negative electrode active material can better balance high energy density, high initial coulombic efficiency, long cycle life, and long storage life.

[0317] Comparative Example 1 uses carbon-coated crystalline silicon as the negative electrode active material. Crystalline silicon exhibits a significant volume effect, while the surface carbon layer offers limited protection. Furthermore, the carbon layer cracks after multiple charge-discharge cycles, leading to repeated damage and reconstruction of the SEI film, increasing the irreversible consumption of active ions. Moreover, the SEI film thickness increases with the number of charge-discharge cycles, consequently increasing the impedance of the secondary battery. Therefore, the secondary battery prepared in Comparative Example 1 exhibits very poor cycle performance.

[0318] In the negative electrode active material prepared in Comparative Example 2, the grain size of the crystalline silicon-based material is uniform. At this time, the crystalline silicon-based material has a large volume expansion and poor structural stability, which leads to poor cycle performance and high volume expansion of the secondary battery. It cannot enable the secondary battery to achieve high energy density, high initial coulombic efficiency, long cycle life and long storage life.

[0319] In the negative electrode active material prepared in Comparative Example 3, the silicon-based material only includes amorphous silicon-based material and does not include crystalline silicon-based material. Since the initial coulombic efficiency of amorphous silicon-based material is low, the actual capacity loss of the secondary battery is large. Therefore, the secondary battery cannot achieve high energy density, high initial coulombic efficiency, long cycle life and long storage life.

[0320] It should be noted that this application is not limited to the above-described embodiments. The above embodiments are merely examples, and any embodiments with the same structure and effect as the technical concept within the scope of this application are included in the technical scope of this application. Furthermore, various modifications that can be conceived by those skilled in the art to the embodiments, and other ways of constructing by combining some of the constituent elements of the embodiments, without departing from the spirit of this application, are also included in the scope of this application.

Claims

1. A negative electrode active material, wherein, The negative electrode active material includes a matrix material and a silicon-based material. The average particle size Dv50 of the negative electrode active material is 4μm-12μm. The matrix material includes a carbon material and has multiple porous structures. At least a portion of the silicon-based material is located within the porous structures of the matrix material. At least a portion of the silicon-based material has a crystalline structure. The silicon-based material includes a first silicon-based material and a second silicon-based material with different grain sizes, and the ratio of the grain size of the first silicon-based material to the grain size of the second silicon-based material is greater than or equal to 1.6:

1. The negative electrode active material extends from the outer surface of the particles to the interior of the particles. The region formed by a distance of 0.5 times the length between any point on the outer surface and the particle core is denoted as the outer region, and the region inside the outer region is denoted as the inner region. In the cross-sectional image of the negative electrode active material, the total cross-sectional area of ​​the first silicon-based material in the outer region is smaller than the total cross-sectional area of ​​the first silicon-based material in the inner region, and the total cross-sectional area of ​​the second silicon-based material in the inner region is smaller than the total cross-sectional area of ​​the second silicon-based material in the outer region. The grain size of the first silicon-based material is greater than 0 and less than or equal to 20 nm, and the grain size of the second silicon-based material is greater than 0 and less than or equal to 12 nm. Furthermore, the grain size of the first silicon-based material and the grain size of the second silicon-based material satisfy any one of the following conditions: (1) The grain size of the first silicon-based material is greater than 12 nm and less than or equal to 20 nm, and the grain size of the second silicon-based material is greater than 0 and less than or equal to 12 nm; (2) The grain size of the first silicon-based material is greater than 8 nm and less than or equal to 12 nm, and the grain size of the second silicon-based material is greater than 0 and less than or equal to 8 nm; (3) The grain size of the first silicon-based material is greater than 5 nm and less than or equal to 8 nm, and the grain size of the second silicon-based material is greater than 0 and less than or equal to 5 nm; (4) The grain size of the first silicon-based material is greater than 2nm and less than or equal to 5nm, and the grain size of the second silicon-based material is greater than 0 and less than or equal to 2nm.

2. The negative electrode active material according to claim 1, wherein, The ratio of the grain size of the first silicon-based material to the grain size of the second silicon-based material is (1.6-4):1; and / or, The grain size of the first silicon-based material is 2nm-20nm; and / or, The grain size of the second silicon-based material is 1nm-12nm.

3. The negative electrode active material according to claim 1, wherein, The ratio of the grain size of the first silicon-based material to the grain size of the second silicon-based material is (2-4):

1.

4. The negative electrode active material according to claim 1, wherein, The ratio α1 of the total cross-sectional area of ​​the first silicon-based material in the outer region to the total cross-sectional area of ​​the first silicon-based material in the inner region is (0-50):100; and / or, The ratio α2 of the total cross-sectional area of ​​the second silicon-based material in the inner region to the total cross-sectional area of ​​the second silicon-based material in the outer region is (0-30):

100.

5. The negative electrode active material according to claim 1, wherein, The ratio α1 of the total cross-sectional area of ​​the first silicon-based material in the outer region to the total cross-sectional area of ​​the first silicon-based material in the inner region is (0-10):100; and / or, The ratio α2 of the total cross-sectional area of ​​the second silicon-based material in the inner region to the total cross-sectional area of ​​the second silicon-based material in the outer region is (0-10):

100.

6. The negative electrode active material according to claim 1, wherein, The cross-sectional image of the negative electrode active material includes a cross-sectional image passing through the particle core of the negative electrode active material.

7. The negative electrode active material according to claim 1, wherein, In the outer region of the cross-sectional image of the negative electrode active material, the ratio β1 of the total cross-sectional area of ​​the first silicon-based material to the total cross-sectional area of ​​the second silicon-based material is (0-25):100; and / or, In the inner region of the cross-sectional image of the negative electrode active material, the ratio β2 of the total cross-sectional area of ​​the first silicon-based material to the total cross-sectional area of ​​the second silicon-based material is 100:(0-250).

8. The negative electrode active material according to claim 1, wherein, In the outer region of the cross-sectional image of the negative electrode active material, the ratio β1 of the total cross-sectional area of ​​the first silicon-based material to the total cross-sectional area of ​​the second silicon-based material is (0-5):100; and / or, In the inner region of the cross-sectional image of the negative electrode active material, the ratio β2 of the total cross-sectional area of ​​the first silicon-based material to the total cross-sectional area of ​​the second silicon-based material is 100:(0-100).

9. The negative electrode active material according to claim 1, wherein, In the outer region of the cross-sectional image of the negative electrode active material, the total cross-sectional area of ​​the first silicon-based material is 0.

10. The negative electrode active material according to claim 1, wherein, In the cross-sectional image of the negative electrode active material, the ratio γ1 of the total cross-sectional area of ​​the first silicon-based material to the total cross-sectional area of ​​the negative electrode active material is greater than 0 and less than or equal to 25%; and / or, In the cross-sectional image of the negative electrode active material, the ratio γ2 of the total cross-sectional area of ​​the second silicon-based material to the total cross-sectional area of ​​the negative electrode active material is greater than or equal to 35% and less than 100%.

11. The negative electrode active material according to claim 1, wherein, In the cross-sectional image of the negative electrode active material, the ratio γ1 of the total cross-sectional area of ​​the first silicon-based material to the total cross-sectional area of ​​the negative electrode active material is 5%-20%; and / or, In the cross-sectional image of the negative electrode active material, the ratio γ2 of the total cross-sectional area of ​​the second silicon-based material to the total cross-sectional area of ​​the negative electrode active material is 40%-60%.

12. The negative electrode active material according to claim 1, wherein, The mass percentage of the first silicon-based material in the silicon-based material is greater than 0 and less than or equal to 40 wt%.

13. The negative electrode active material according to claim 1, wherein, The mass percentage of the first silicon-based material in the silicon-based material is 10wt%-30wt%.

14. The negative electrode active material according to claim 1, wherein, At least a portion of the silicon-based material is located within the porous structure of the matrix material, and there are voids between the silicon-based material and the matrix material.

15. The negative electrode active material according to claim 1, wherein, The first silicon-based material includes one or more of elemental silicon, silicon oxide, silicon-carbon materials, silicon-nitrogen composites, and silicon alloys; and / or, The second silicon-based material includes one or more of elemental silicon, silicon oxide, silicon-carbon materials, silicon-nitrogen composites, and silicon alloy materials.

16. The negative electrode active material according to claim 1, wherein, The first silicon-based material comprises elemental silicon, and the grain size of the first silicon-based material is greater than 0 and less than or equal to 8 nm; and / or, The second silicon-based material comprises elemental silicon, and the grain size of the second silicon-based material is greater than 0 and less than or equal to 5 nm.

17. The negative electrode active material according to claim 1, wherein, The first silicon-based material comprises elemental silicon, and the grain size of the first silicon-based material is 2nm-8nm; and / or, The second silicon-based material comprises elemental silicon, and the grain size of the second silicon-based material is 1nm-5nm.

18. The negative electrode active material according to claim 1, wherein, The matrix material satisfies at least one of the following conditions (1) to (3): (1) The porosity of the matrix material is 30%-60%; (2) The average particle size Dv50 of the matrix material is 4μm-12μm; (3) The carbon material includes one or more of graphite materials, activated carbon, biomass carbon, pyrolytic carbon and resin carbon.

19. The negative electrode active material according to claim 1, wherein, The negative electrode active material further includes a coating layer, which is located on at least a portion of the surface of the matrix material. The covering layer satisfies at least one of the following conditions (1) to (2): (1) The coating layer includes one or more of carbon materials, conductive polymers, metal oxides and metal sulfides; (2) The thickness of the coating layer is 0nm-200nm.

20. The negative electrode active material according to claim 1, wherein, The negative electrode active material comprises carbon and silicon, wherein the mass percentage of carbon in the negative electrode active material is 40wt%-60wt%. The silicon content in the negative electrode active material is 38wt%-58wt%.

21. The negative electrode active material according to claim 1, wherein, The pore volume of the negative electrode active material is 0.001 cm³. 3 / g-0.02cm 3 / g; and / or, The BET specific surface area of ​​the negative electrode active material is 1m². 2 / g-15m 2 / g.

22. A method for preparing a negative electrode active material, comprising the following steps: providing a matrix material comprising a plurality of pore structures; dispersing a silicon-based material into the pore structures of the matrix material to obtain the negative electrode active material, wherein, The negative electrode active material includes a matrix material and a silicon-based material. The average particle size Dv50 of the negative electrode active material is 4μm-12μm. The matrix material includes a carbon material and has multiple porous structures. At least a portion of the silicon-based material is located within the porous structures of the matrix material. At least a portion of the silicon-based material has a crystalline structure. The silicon-based material includes a first silicon-based material and a second silicon-based material with different grain sizes, and the ratio of the grain size of the first silicon-based material to the grain size of the second silicon-based material is greater than or equal to 1.6:

1. The length extending from the outer surface of the negative electrode active material towards the interior of the particle from any point on the outer surface of the particle to the particle core is 0. The region defined by a distance of 0.5 times is denoted as the outer region, and the region inside the outer region is denoted as the inner region. In the cross-sectional image of the negative electrode active material, the total cross-sectional area of ​​the first silicon-based material in the outer region is smaller than the total cross-sectional area of ​​the first silicon-based material in the inner region, and the total cross-sectional area of ​​the second silicon-based material in the inner region is smaller than the total cross-sectional area of ​​the second silicon-based material in the outer region. The grain size of the first silicon-based material is greater than 0 and less than or equal to 20 nm, and the grain size of the second silicon-based material is greater than 0 and less than or equal to 12 nm. Furthermore, the grain sizes of the first and second silicon-based materials satisfy any one of the following conditions: (1) The grain size of the first silicon-based material is greater than 12 nm and less than or equal to 20 nm, and the grain size of the second silicon-based material is greater than 0 and less than or equal to 12 nm; (2) The grain size of the first silicon-based material is greater than 8 nm and less than or equal to 10 nm, and the grain size of the second silicon-based material is greater than 0 and less than or equal to 8 nm; (3) The grain size of the first silicon-based material is greater than 5 nm and less than or equal to 8 nm, and the grain size of the second silicon-based material is greater than 0 and less than or equal to 5 nm; (4) The grain size of the first silicon-based material is greater than 2nm and less than or equal to 5nm, and the grain size of the second silicon-based material is greater than 0 and less than or equal to 2nm.

23. The preparation method according to claim 22, wherein, The steps of dispersing silicon-based materials into the porous structure of the matrix material include the following steps: placing the matrix material, which includes multiple porous structures, as a substrate in a reactor, introducing a first mixed gas containing silicon source gas, and depositing at a first temperature T1 for a first time t1, after which the introduction of the first mixed gas is stopped; after the temperature inside the reactor drops to a second temperature T2, introducing a second mixed gas containing silicon source gas, and depositing at the second temperature T2 for a second time t2, after which the negative electrode active material is obtained. The region formed by extending from the outer surface of the negative electrode active material towards the interior of the particle, a distance equal to 0.5 times the length between any point on the outer surface of the particle and the particle core, is designated as the outer region. The region inside the outer region is designated as the inner region. In the cross-sectional image of the negative electrode active material, the total cross-sectional area of ​​the first silicon-based material in the outer region is smaller than the total cross-sectional area of ​​the first silicon-based material in the inner region, and the total cross-sectional area of ​​the second silicon-based material in the inner region is smaller than the total cross-sectional area of ​​the second silicon-based material in the outer region.

24. The preparation method according to claim 23, wherein, Before introducing the first mixed gas containing silicon source gas, the process includes the following steps: placing a matrix material with multiple pore structures as a substrate in the reactor, and performing purging and preheating treatment using a protective gas.

25. The preparation method according to claim 23, wherein, The volume percentage V1 of the silicon source gas in the first mixture is greater than the volume percentage V2 of the silicon source gas in the second mixture; and / or, T1>T2; and / or, t1 <t2。 26. The preparation method according to claim 23, wherein, The first mixed gas includes a silicon source gas and a protective gas; and / or, The total gas flow rate of the first mixed gas is 0.5 L / min - 20 L / min; and / or, The first temperature T1 is 500℃-700℃; and / or, The first time interval t1 is 0.5h-8h.

27. The preparation method according to claim 23, wherein, The second mixture includes a silicon source gas and a protective gas; and / or, The total gas flow rate of the second mixture is 0.5 L / min - 20 L / min; and / or, The second temperature T2 is 500℃-600℃; and / or, The second time t2 is 4h-20h; and / or, The total gas flow rate of the second mixture is the same as the total gas flow rate of the first mixture.

28. The preparation method according to claim 23 further comprises the following step: forming a coating layer on at least the surface of the obtained negative electrode active material, said coating layer comprising one or more of carbon materials, conductive polymers, metal oxides and metal sulfides.

29. The preparation method according to claim 28, wherein, The step of forming the coating layer includes the following steps: placing the obtained negative electrode active material in a reactor, introducing a third mixed gas containing carbon source gas, and depositing it at a third temperature T3 for a third time t3 to obtain a carbon-coated negative electrode active material.

30. The preparation method according to claim 29, wherein, The third mixture includes a carbon source gas and a protective gas; and / or, The total gas flow rate of the third mixture is 0.5 L / min - 20 L / min; and / or The third temperature T3 is 600℃-800℃; and / or, The third time interval t3 is 0.5h-4h.

31. A secondary battery, comprising a negative electrode sheet, wherein the negative electrode sheet comprises the negative electrode active material according to any one of claims 1-21 or the negative electrode active material prepared by the preparation method according to any one of claims 22-30.

32. An electrical device comprising the secondary battery as described in claim 31.

Citation Information

Patent Citations

  • Negative pole piece, electrochemical device and electronic device

    CN111261834A

  • Negative active material for rechargeable lithium battery, method of preparing the same, and rechargeable lithium battery including the same

    KR1020130107892A